3D screen printing – An innovative technology for large-scale manufacturing of pharmaceutical dosage forms - Moldenhauer, Daniel; Nguyen, Doan Chau Yen; Jescheck, Lisa; Hack, Franz; Fischer, Dagmar; Schneeberger, Achim (International Journal of Pharmaceutics, 2021)
Three-dimensional (3D) screen printing was used to fabricate oral dosage forms of different geometry and size. The paste required as starting material for the 3D screen printing process was designed for delayed release and contained the model drug paracetamol (acetaminophen). A prototype screen printing unit was used to fabricate different tablets in a single production process. The resulting tablets were produced with three different sizes and designed geometries (disk, donut, cuboid, oval and grid). Investigation of size and mass of the individual tablets demonstrated high uniformity within the various groups of tablets. Further characterization of their physical properties, such as breaking force and friability, yielded results comparing favorably to conventionally produced tablets. Finally, drug release tests in artificial gastric media showed paracetamol release to depend on the surface-area-to-volume ratio. In conclusion, the study shows the potential of 3D screen printing to fabricate more complex oral dosage forms in the setting of mass production with high reproducibility.
CRIS-Team Scopus Importer:2021-01-15
Keywords: 3D printing; 3D screen printing; Additive manufacturing; Controlled release; Drug delivery system; Paracetamol

3D screen printing technology enables fabrication of oral drug dosage forms with freely tailorable release profiles - Enke, Marcel; Schwarz, Nicolle; Gruschwitz, Franka; Winkler, Daniela; Hanf, Felix; Jescheck, Lisa; Seyferth, Stefan; Fischer, Dagmar; Schneeberger, Achim (International Journal of Pharmaceutics, 2023)
3D printing offers new opportunities to customize oral dosage forms of pharmaceuticals for different patient populations, improving patient safety, care, and compliance. Although several notable 3D print technologies have been developed, such as inkjet printing, powder-based printing, selective laser sintering (SLS) printing, and fused deposition modelling (FDM), among others, their capacity is often limited by the number of printing heads. 3D screen-printing (3DSP) is based on a classic flatbed screen printing that is widely used in industrial applications for technical applications. 3DSP can build up thousands of units per screen simultaneously, enabling mass customization of pharmaceuticals. Here, we use 3DSP to investigate two novel paste formulations: immediate-release (IR) and extended-release (ER) using Paracetamol (acetaminophen) as the active pharmaceutical ingredient (API). Both disk-shaped and donut-shaped tablets were fabricated using one or both pastes to design drug delivery systems (DDS) with tailored API release profiles. The size and mass of the produced tablets demonstrated high uniformity. Characterization of the tablets physical properties, such as breaking force (25–39 N) and friability (0.002–0.237%), adhering to Ph. Eur (10th edition). Finally, drug release tests with a phosphate buffer at pH 5.8 showed Paracetamol release depended on the IR- and ER paste materials and their respective compartment size of the composite DDS, which can be readily varied using 3DSP. This work further demonstrates the potential of 3DSP to manufacture complex oral dosage forms exhibiting custom release functionalities for mass production.
CRIS-Team Scopus Importer:2023-06-30
Keywords: 3D printing; 3D screen printing; Additive manufacturing; Controlled release; Drug delivery system; Extended-release; Immediate-release; Paracetamol

4-Methylcatechol, a Flavonoid Metabolite with Potent Antiplatelet Effects - Applova, Lenka; Karlickova, Jana; Warncke, Paul; Macakova, Katerina; Hrubsa, Marcel; Machaek, Miloslav; Tvrdy, Vaclav; Fischer, Dagmar; Mladenka, Premysl (Molecular Nutrition & Food Research, 2019)
Scope: Intake of flavonoids from the diet can be substantial, and epidemiological studies suggest that these compounds can decrease the incidence of cardiovascular diseases by involvement with increased platelet aggregation. Although parent flavonoids possess antiplatelet effects, the clinical importance is disputable due to their very low bioavailability. Most of them are metabolized by human colon bacteria to smaller phenolic compounds, which reach higher plasma concentrations than the parent flavonoids. In this study, a series of 29 known flavonoid metabolites is tested for antiplatelet potential. Methods and results: Four compounds appear to have a biologically relevant antiplatelet effect using whole human blood. 4-Methylcatechol (4-MC) is clearly the most efficient being about 10× times more active than clinically used acetylsalicylic acid. This ex vivo effect is also confirmed using a potentially novel in-vivo-like ex ovo hen's egg model of thrombosis, where 4-MC significantly increases the survival of the eggs. The mechanism of action is studied and it seems that it is mainly based on the influence on intracellular calcium signaling. Conclusion: This study shows that some flavonoid metabolites formed by human microflora have a strong antiplatelet effect. This information can help to explain the antiplatelet potential of orally given flavonoids.
CRIS-Team Scopus Importer:2020-10-13
Keywords: 4-methylcatechol; aggregation; flavonoids; metabolites; platelets; pyrogallol

A blue fluorescent labeling technique utilizing micro-and nanoparticles for tracking in LIVE/DEAD® stained pathogenic biofilms of staphylococcus aureus and burkholderia cepacia - Klinger-Strobel, Mareike; Ernst, Julia; Lautenschlaeger, Christian; Pletz, Mathias W.; Fischer, Dagmar; Makarewicz, Oliwia (International Journal of Nanomedicine, 2016)
Strategies that target and treat biofilms are widely applied to bacterial cultures using popular live/dead staining techniques with mostly red or green fluorescent markers (eg, with SYTO® 9, propidium iodide, fluorescein). Therefore, visualizing drugs or micro-and nanoparticulate delivery systems to analyze their distribution and effects in biofilms requires a third fluorescent dye that does not interfere with the properties of the live/dead markers. The present study establishes and evaluates a model for tracking polymeric particles in fluorescently stained biological material. To this end, poly(d,l-lactide-co-glycolide) (PLGA)-based micro-and nanoparticles were used as well-established model systems, which, because of their favorable safety profiles, are expected to play important future roles with regard to drug delivery via inhalation. PLGA was covalently and stably labeled with 7-amino-4-methyl-3-coumarinylacetic acid (AMCA), after which blue fluorescent poly(ethylene glycol)-block-PLGA (PEG-PLGA) particles were prepared using a mixture of fluorescent AMCA-PLGA and PEG-PLGA. Because chitosan is known to reduce negative surface charge, blue fluorescent PEG-PLGA-particles with chitosan were also prepared. These micro-and nanoparticles were physicochemically characterized and could be clearly distinguished from live/dead stained bacteria in biofilms using confocal laser scanning microscopy.
CRIS-Team Scopus Importer:2020-10-13
Keywords: 7-amino-4-methyl-3-coumarinylacetic acid; Chitosan; Confocal laser scanning microscopy; Cystic fibrosis; Hydrodynamic diameter; PEG; PLGA

Active wound dressings based on bacterial nanocellulose as drug delivery system for octenidine - Moritz, Sebastian; Wiegand, Cornelia; Wesarg, Falko; Hessler, Nadine; Mueler, Frank A.; Kralisch, Dana; Hipler, Uta-Christina; Fischer, Dagmar (International Journal of Pharmaceutics, 2014)
Although bacterial nanocellulose (BNC) may serve as an ideal wound dressing, it exhibits no antibacterial properties by itself. Therefore, in the present study BNC was functionalized with the antiseptic drug octenidine. Drug loading and release, mechanical characteristics, biocompatibility, and antimicrobial efficacy were investigated. Octenidine release was based on diffusion and swelling according to the Ritger-Peppas equation and characterized by a time dependent biphasic release profile, with a rapid release in the first 8 h, followed by a slower release rate up to 96 h. The comparison between lab-scale and up-scale BNC identified thickness, water content, and the surface area to volume ratio as parameters which have an impact on the control of the release characteristics. Compression and tensile strength remained unchanged upon incorporation of octenidine in BNC. In biological assays, drug-loaded BNC demonstrated high biocompatibility in human keratinocytes and antimicrobial activity against Staphylococcus aureus. In a long-term storage test, the octenidine loaded in BNC was found to be stable, releasable, and biologically active over a period of 6 months without changes. In conclusion, octenidine loaded BNC presents a ready-to-use wound dressing for the treatment of infected wounds that can be stored over 6 months without losing its antibacterial activity. © 2014 Elsevier B.V.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Antiseptic; Hydrogel; Nanocellulose; Octenidine; Wound dressing

Amino Acid–Substituted Dextran-Based Non-Viral Vectors for Gene Delivery - Zink, Matthias; Hotzel, Konrad; Schubert, Ulrich S.; Heinze, Thomas; Fischer, Dagmar (Macromolecular Bioscience, 2019)
To form bio-inspired non-viral vectors for DNA delivery, the polysaccharide dextran is allowed to react with Boc-amino protected amino acids glycine, β-alanine, and L-lysine activated with 1,1’-carbonyldiimidazole and subsequent dextran ester deprotection. A library of such dextran esters is made available to investigate the relationship between polymer structure, complex formation, stability, toxicity, and transfection. Only dextran esters of β-alanine and L-lysine are able to efficiently interact with DNA as shown by dye exclusion assays, to form nanosized complexes (70–110 nm) with positive zeta potential. With increasing substitution degree and complex charge ratios, the L-lysine esters accomplish more effective binding and protection of DNA against enzymatic degradation than β-alanine esters. However, luciferase reporter gene assays reveal higher transfection for β-alanine than for L-lysine esters due to a more effective DNA release and better suited buffing area of the amino groups triggering the endosomal release. Conclusively, β-alanine-substituted dextran derivatives may serve as promising non-viral vectors.
CRIS-Team Scopus Importer:2020-10-13
Keywords: amino acid; dextran ester; gene delivery; polysaccharides; transfection

Analysis of HDACi-Coupled Nanoparticles: Opportunities and Challenges - Kühne, Marie; Hofmann, Susanne; Lindemann, Henry; Cseresnyés, Zoltán; Dzierza, Andreas; Schröder, Daniel; Godmann, Maren; Koschella, Andreas; Eggeling, Christian; Fischer, Dagmar; Figge, Marc Thilo; Heinze, Thomas; et al. (Methods in Molecular Biology, 2023)
Systemic administration of histone deacetylase inhibitors (HDACi), like valproic acid (VPA), is often associated with rapid drug metabolization and untargeted tissue distribution. This requires high-dose application that can lead to unintended side effects. Hence, drug carrier systems such as nanoparticles (NPs) are developed to circumvent these disadvantages by enhancing serum half-life as well as organ specificity.This chapter gives a summary of the biological characterization of HDACi-coupled NPs in vitro, including investigation of cellular uptake, biocompatibility, as well as intracellular drug release and activity. Suitable methods, opportunities, and challenges will be discussed to provide general guidelines for the analysis of HDACi drug carrier systems with a special focus on recently developed cellulose-based VPA-coupled NPs.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Biocompatibility; Cellular uptake; Cellulose; Drug delivery system; Hemocompatibility; Histone deacetylase inhibitor; Imaging; Nanoparticle; Shell-less hen’s egg model; Valproic acid

A novel computerized cell count algorithm for biofilm analysis - Klinger-Strobel, Mareike; Suesse, Herbert; Fischer, Dagmar; Pletz, Mathias W.; Makarewicz, Oliwia (PLoS ONE, 2016)
Biofilms are the preferred sessile and matrix-embedded life form of most microorganisms on surfaces. In the medical field, biofilms are a frequent cause of treatment failure because they protect the bacteria from antibiotics and immune cells. Antibiotics are selected according to the minimal inhibitory concentration (MIC) based on the planktonic form of bacteria. Determination of the minimal biofilm eradicating concentration (MBEC), which can be up to 1,000-fold greater than the MIC, is not currently conducted as routine diagnostic testing, primarily because of the methodical hurdles of available biofilm assessing protocols that are time- and cost-consuming. Comparative analysis of biofilms is also limited as most quantitative methods such as crystal violet staining are indirect and highly imprecise. In this paper, we present a novel algorithm for assessing biofilm resistance to antibiotics that overcomes several of the limitations of alternative methods. This algorithm aims for a computer-based analysis of confocal microscope 3D images of biofilms after live/dead stains providing various biofilm parameters such as numbers of viable and dead cells and their vertical distributions within the biofilm, or biofilm thickness. The performance of this algorithm was evaluated using computer-simulated 2D and 3D images of coccal and rodent cells varying different parameters such as cell density, shading or cell size. Finally, genuine biofilms that were untreated or treated with nitroxoline or colistin were analyzed and the results were compared with quantitative microbiological standard methods. This novel algorithm allows a direct, fast and reproducible analysis of biofilms after live/dead staining. It performed well in biofilms of moderate cell densities in a 2D set-up however the 3D analysis remains still imperfect and difficult to evaluate. Nevertheless, this is a first try to develop an easy but conclusive tool that eventually might be implemented into routine diagnostics to determine the MBEC and to improve outcomes of patients with biofilm-associated infections.
CRIS-Team Scopus Importer:2020-10-13

A novel method for the assessment of targeted PEI-based nanoparticle binding based on a static surface plasmon resonance system - Hoebel, Sabrina; Vornicescu, Doru; Bauer, Marius; Fischer, Dagmar; Keusgen, Michael; Aigner, Achim (Analytical Chemistry, 2014)
The delivery of nucleic acids is a major hurdle in gene therapy or therapeutic gene knockdown, and the development of intelligent and safe nanoparticles as carrier systems is thus under intense investigation. The introduction of ligands for their targeted delivery is of major interest. Here, we describe a novel approach for the analysis of the binding properties of antibody-functionalized nanoparticles, using surface plasmon resonance (SPR) in a static cuvette system. By chemical coupling of the Epidermal Growth Factor Receptor (EGFR)-specific antibody cetuximab to poly(ethylene imine) (PEI) via a PEG-spacer and subsequent DNA or siRNA complexation, we generated targeted nanoplexes with low surface charge. Antibody-mediated uptake into EGFR overexpressing cells was observed. SPR measurements with use of a novel, protein A-based sandwich system for the immobilization of the target receptor in its correct steric orientation allowed the analysis of the specific PEI-PEG-cetuximab binding to EGFR and the determination of binding affinities. Importantly, our cuvette-based SPR assay system was also suitable for the monitoring of ligand-mediated nanoparticle binding, without convection or shear stress. We conclude that our SPR sandwich system allows the precise analysis of the binding of ligand-functionalized nanoparticles in real-time, and we thus establish SPR for the in vitro evaluation of ligand modifications for generating targeted nanoparticles. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2020-10-13

Antifungal effect of cold atmospheric plasma in a 3D model of cutaneous candidiasis - Fink, S.; Fischer, M.; Stubenrauch, M.; Horn, K.; Spange, S.; Pfuch, A.; Muller, J.; Fischer, Dagmar; Wiegand, C. (MYCOSES, 2022)
CRIS-Team WoS Importer:2022-09-23

Anti-inflammatory celastrol promotes a switch from leukotriene biosynthesis to formation of specialized pro-resolving lipid mediators - Pace, Simona; Zhang, Kehong; Jordan, Paul M.; Bilancia, Rossella; Wang, Wenfei; Börner, Friedemann; Hofstetter, Robert K.; Potenza, Marianna; Kretzer, Christian; Gerstmeier, Jana; Fischer, Dagmar; Lorkowski, Stefan; et al. (Pharmacological research, 2021)
The pentacyclic triterpenoid quinone methide celastrol (CS) from Tripterygium wilfordii Hook. F. effectively ameliorates inflammation with potential as therapeutics for inflammatory diseases. However, the molecular mechanisms underlying the anti-inflammatory and inflammation-resolving features of CS are incompletely understood. Here we demonstrate that CS potently inhibits the activity of human 5-lipoxygenase (5-LOX), the key enzyme in pro-inflammatory leukotriene (LT) formation, in cell-free assays with IC50 = 0.19–0.49 µM. Employing metabololipidomics using ultra-performance liquid chromatography coupled to tandem mass spectrometry in activated human polymorphonuclear leukocytes or M1 macrophages we found that CS (1 µM) potently suppresses 5-LOX-derived products without impairing the formation of lipid mediators (LM) formed by 12-/15-LOXs as well as fatty acid substrate release. Intriguingly, CS induced the generation of 12-/15-LOX-derived LM including the specialized pro-resolving mediator (SPM) resolvin D5 in human M2 macrophages. Finally, intraperitoneal pre-treatment of mice with 10 mg/kg CS strongly impaired zymosan-induced LT formation and simultaneously elevated the levels of SPM and related 12-/15-LOX-derived LM in peritoneal exudates, spleen and plasma in vivo. Conclusively, CS promotes a switch from LT biosynthesis to formation of SPM which may underlie the anti-inflammatory and inflammation-resolving effects of CS, representing an interesting pharmacological strategy for intervention with inflammatory disorders.
CRIS-Team Scopus Importer:2021-04-19
Keywords: 5-lipoxygenase; arachidonic acid (PubChem CID: 444899); Celastrol; celastrol (PubChem CID: 122724); celecoxib (PubChem CID: 2662); dimethyl sulfoxide (PubChem CID: 679); indomethacin (PubChem CID: 3715); Inflammation; Leukotriene; MK886 (PubChem CID: 3651377); resolvin D5 (PubChem CID: 16061139); Specialized pro-resolving mediators; zileuton (PubChem CID: 60490); zymosan (PubChem CID: 64689)

Anti-Influenza Activity of 6BIGOE: Improved Pharmacological Profile After Encapsulation in PLGA Nanoparticles - Schroeder, Josefine; Westhoff, Jan; Vilotijević, Ivan; Werz, Oliver; Hoeppener, Stephanie; Löffler, Bettina; Fischer, Dagmar; Ehrhardt, Christina (International Journal of Molecular Sciences, 2025)
Influenza A virus (IAV) infections continue to threaten public health. Current strategies, such as vaccines and antiviral drugs, are limited due to their time-consuming development and drug-resistant strains. Therefore, new effective treatments are needed. Here, virus-supportive cellular factors are promising drug targets, and the encapsulation of candidate substances in poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) is intended to improve their bioavailability. This study investigates the potential of the indirubin derivative 6-bromoindirubin-3′-glycerol-oxime ether (6BIGOE), a glycogen synthase kinase 3 (GSK-3)β inhibitor, for its potential to regulate IAV replication in vitro. The effects of 6BIGOE-loaded PLGA NPs on cell metabolism were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) assays in A549 and Calu-3 cells. Viral replication and spread were monitored in various IAV-infected cell lines in the absence and presence of free and 6BIGOE-loaded PLGA NPs via plaque assays and Western blot analysis. The encapsulation of 6BIGOE in PLGA NPs resulted in reduced negative side effects on cell viability while maintaining antiviral efficacy. Both encapsulated and free 6BIGOE exhibited antiviral activity, potentially through GSK-3β inhibition and the disruption of key signaling pathways required for viral replication. The data indicate 6BIGOE, particularly after encapsulation in NPs, as a potential candidate for further investigation and development as an antiviral agent to treat IAV infections.
CRIS-Team Scopus Importer:2025-05-23
Keywords: antiviral; glycogen synthase kinase 3 (GSK-3); indirubin; influenza A virus (IAV); nanoparticles (NPs); poly(D; L-lactic-co-glycolic acid) (PLGA)

Antimicrobial functionalization of bacterial nanocellulose by loading with polihexanide and povidone-iodine - Wiegand, Cornelia; Moritz, Sebastian; Hessler, Nadine; Kralisch, Dana; Wesarg, Falko; Mueller, Frank A.; Fischer, Dagmar; Hipler, Uta-Christina (Journal of Materials Science: Materials in Medicine, 2015)
Bacterial nanocellulose (BNC) is chemically identical with plant cellulose but free of byproducts like lignin, pectin, and hemicelluloses, featuring a unique reticulate network of fine fibers. BNC sheets are mostly obtained by static cultivation. Now, a Horizontal Lift Reactor may provide a cost efficient method for mass production. This is of particular interest as BNC features several properties of an ideal wound dressing although it exhibits no bactericidal activity. Therefore, BNC was functionalized with the antiseptics povidone-iodine (PI) and polihexanide (PHMB). Drug loading and release, mechanical characteristics, biocompatibility, and antimicrobial efficacy were investigated. Antiseptics release was based on diffusion and swelling according to Ritger–Peppas equation. PI-loaded BNC demonstrated a delayed release compared to PHMB due to a high molar drug mass and structural changes induced by PI insertion into BNC that also increased the compressive strength of BNC samples. Biological assays demonstrated high biocompatibility of PI-loaded BNC in human keratinocytes but a distinctly lower antimicrobial activity against Staphylococcus aureus compared to PHMB-loaded BNC. Overall, BNC loaded with PHMB demonstrated a better therapeutic window. Moreover, compressive and tensile strength were not changed by incorporation of PHMB into BNC, and solidity during loading and release could be confirmed.
CRIS-Team Scopus Importer:2020-10-13

Application of a three-fluid nozzle for the preparation of amorphous solid dispersions - Corell, Carolina; Seyferth, Stefan; Fischer, Dagmar; Schiffter, Heiko A. (Drying Technology, 2023)
In this work, the manufacture of amorphous solid dispersions of poorly water-soluble carbamazepine using a laboratory spray drying setup with a three-fluid nozzle and two separate liquid feed solutions of (a) the active and (b) the polymeric excipient (copovidone or basic butylated methacrylate copolymer) was investigated and compared to a traditional two-fluid nozzle setup. Results show that particles with the desired drug content were manufactured using the three-fluid nozzle setup. Amorphous solid dispersion could be obtained up to a drug load of 50% (w/w) processing solutions with miscible solvents and copovidone as polymer. Higher active concentrations, the use of immiscible solvents or switching of the capillaries led to a substantial crystallization of carbamazepine as seen in XRD and DSC analysis. The polymorphic form IV of carbamazepine was formed in the presence of copovidone at high solid concentrations of the liquid feed.
CRIS-Team Scopus Importer:2023-03-03
Keywords: amorphous solid dispersions; crystallization; nozzle; solubility; Spray drying

A shell-less hen's egg test as infection model to determine the biocompatibility and antimicrobial efficacy of drugs and drug formulations against Pseudomonas aeruginosa - Warncke, Paul; Fink, Sarah; Wiegand, Cornelia; Hipler, Uta-Christina; Fischer, Dagmar (International Journal of Pharmaceutics, 2020)
A shell-less hen's egg based infection test with Pseudomonas aeruginosa was established to investigate the antimicrobial efficacy of drugs and drug formulations close to the in vivo situation. The test system using preincubated fertilized chicken eggs transferred in petri dishes was optimized with respect to the controlled local application of liquid materials and bacteria as well as the bacterial cultivation conditions. The applicability of the ex ovo infection model was confirmed with antimicrobial susceptibility tests using tobramycin, ciprofloxacin and meropenem. The validity of the ex ovo data was demonstrated by correlation with in vitro data of the CellTiter®-Blue and the microplate laser nephelometry assay. Real-time imaging of the progress of infection and the efficacy of the treatment could be realized by the MolecuLight i:X™ technique. Furthermore, in a proof-of-concept efficacy, biocompatibility and even the presence of irritants were determined side-by-side using commercial ophthalmics. In conclusion, this egg based infection model could bridge the gap between in vitro and in vivo models for the evaluation of antimicrobial susceptibility to reduce animal tests according to the 3R concept.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Antibiotics; Antimicrobial; Cytotoxicity; Eye drops; Hen's egg; Pseudomonas aeruginosa

Aspects of pulmonary drug delivery strategies for infections in cystic fibrosis-where do we stand? - Klinger-Strobel, Mareike; Lautenschlaeger, Christian; Fischer, Dagmar; Mainz, Jochen G.; Bruns, Tony; Tuchscherr, Lorena; Pletz, Mathias W.; Makarewicz, Oliwia (Expert Opinion on Drug Delivery, 2015)
Introduction: Cystic fibrosis (CF) is the most common life-shortening hereditary disease among Caucasians and is associated with severe pulmonary damage because of decreased mucociliary clearance and subsequent chronic bacterial infections. Approximately 90% of CF patients die from lung destruction, promoted by pathogens such as Pseudomonas aeruginosa. Consequently, antibiotic treatment is a cornerstone of CF therapy, preventing chronic infection and reducing bacterial load, exacerbation rates and loss of pulmonary function. Many drugs are administered by inhalation to achieve high pulmonary concentration and to lower systemic side effects. However, pulmonary deposition of inhaled drugs is substantially limited by bronchial obstruction with viscous mucus and restrained by intrapulmonary bacterial biofilms.Areas covered: This review describes challenges in the therapy of CF-associated infections by inhaled antibiotics and summarizes the current state of microtechnology and nanotechnology-based pulmonary antibiotic delivery strategies. Recent and ongoing clinical trials as well as experimental approaches for microparticle/nanoparticle-based antibiotics are presented and their advantages and disadvantages are discussed.Expert opinion: Rapidly increasing antimicrobial resistance accompanied by the lack of novel antibiotics force targeted and more efficient use of the available drugs. Encapsulation of antimicrobials in nanoparticles or microparticles of organic polymers may have great potential for use in CF therapy.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Amikacin; Aztreonam lysine; Biofilms; Burkholderia cepacia complex; Colistin; Nanoparticles; Poly(lactic-co-glycolic acid); Pseudomonas aeruginosa; Staphylococcus aureus; Tobramycin

Bacterial cellulose cookbook: A systematic review on sustainable and cost-effective substrates - Quijano, Luis; Rodrigues, Raquel; Fischer, Dagmar; Tovar-Castro, Jorge David; Payne, Alice; Navone, Laura; Hu, Yating; Yan, Hao; Pinmanee, Phitsanu; Poon, Edgar; Yang, Jing He; Barro, Eve (Journal of Bioresources and Bioproducts, 2024)
Bacterial cellulose is a versatile material with applications in many industries. However, the widespread uptake of bacterial cellulose faces challenges including high production costs and lack of scalability. One approach to address these obstacles is the use of alternative substrates and media, compared to the Hestrin–Schramm (HS) media. By evaluating and selecting appropriate media and substrates, the production of bacterial cellulose can be more efficient: enabling sustainable systems and supply chains where less energy and materials are lost, and the output production is increased. The purpose of this paper is to analyze the current landscape of bacterial cellulose alternative media and substrates (ingredients). Through a systematic review of 198 papers, this review identifies 299 alternative substrates from 12 industries and 101 bacterial cellulose-producing strains, which were systematically compared. This review also finds that there are methodological gaps in this field such as data variability, papers mislabelling the HS media or not using a comparison media, and a lack of strain names. This alternative substrate analysis for bacterial cellulose production demonstrates that overall, for some applications alternative substrates can be taken into consideration that are not only cheaper, but also produce higher yields than HS media.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Bacterial cellulose; Cost-effective; Fermentation; Hestrin–Schramm; Substrates; Sustainability; Systematic review

Bacterial nanocellulose patches as a carrier for hydrating formulations to improve the topical treatment of nail diseases - Bellmann, Tom; Luber, Ruth; Kischio, Lisa; Karl, Berit; Poetzinger, Yvette; Beekmann, Uwe; Kralisch, Dana; Wiegand, Cornelia; Fischer, Dagmar (International Journal of Pharmaceutics, 2022)
Bacterial nanocellulose has been widely investigated for wound healing applications, mainly due to its mois-turizing capabilities and biocompatibility. Even though the topical therapy of nail diseases could benefit from these properties, this application has not yet been investigated. Therefore, actively hydrating nail patches based on bacterial nanocellulose were developed to improve the delivery of ciclopirox olamine and Boswellia serrata extract through the nail plate. The nanocellulose matrix was used to enable the application of hydration enhancing solutions based on glycerol and urea as a mechanically stable patch. While the favorable mechanical characteristics of the material remained unchanged, an increase of the incorporated glycerol concentration enhanced the transparency and wetting capacity of the patches. A biphasic drug release from the patches could be observed for drug and extract with a faster release for the hydrophilic ciclopirox olamine. High glycerol concentrations correlated with increased cumulative release and permeation through keratin films for drug and extract, demonstrating the hydration driven permeation enhancement. Patches containing ciclopirox olamine showed strong antimycotic effects against relevant pathogens for onychomycosis. The present finding proposed the combination of bacterial nanocellulose with glycerol, urea and different drug as a promising platform for the local treatment of nail diseases.
CRIS-Team WoS Importer:2022-11-18

Bacterial nanocellulose: Reinforcement of compressive strength using an adapted Mobile Matrix Reservoir Technology and suitable post-modification strategies - Rothe, Holger; Rost, Juergen; Kramer, Friederike; Alkhatib, Yaser; Petzold-Welcke, Katrin; Klemm, Dieter; Fischer, Dagmar; Liefeith, Klaus (Journal of the Mechanical Behavior of Biomedical Materials, 2022)
Bacterial nanocellulose (BNC) is a highly interesting biomaterial due to some outstanding properties especially when used in medical therapeutics and diagnostics. BNC is absolutely bioinert and is characterised by intrinsic properties such as high tensile stiffness and elasticity, high porosity, exceptional water uptake and swelling capacity. Furthermore, these properties can be adjusted in a very defined way by specifically changing the cultivation conditions or performing post-modifications such as crosslinking, functionalisation with additives, dehydration or drying. Especially the high tensile strength of the nanofibrillar material has been the subject of many investigations in the past couple of years. Nevertheless, the enormous tensile strength and elasticity of BNC is contrary to an almost purely viscous behaviour under compressive load. In the present study, different methods to influence the mechanical behaviour under compression with respect to load bearing applications of BNC are systematically investigated. The possibilities and limitations of the variable layer-by-layer cultivation known as Mobile Matrix Reservoir Technology (MMR-Tech) as well as the effect of different post-modification strategies of BNC are thoroughly investigated. Beside of commonly used indentation tests for characterising the mechanical properties of BNC, we introduce a novel evaluation methodology based on mechanical relaxation measurements and an evolutionary regression algorithm for the derivation of a viscoelastic material law, which for the first time allows standardised, comparative viscoelastic investigations of soft-matter biomaterials to be performed independently of the measurement setup. Using this methodology, we are able to show, that cultivation conditions for BNC and suitable post modifications can result in different effects on the viscoelastic behaviour of the fabricated composites. We show that the cultivation conditions for BNC primarily affect the height of dispersion and the frequency of the relaxation centre which corresponds roughly to the mean value of the logarithmic distributed relaxation times, and that these effects could be enhanced by post-modifications. However, we also identify parameters, such as the width of the relaxation region, which corresponds roughly to the standard deviation of the logarithmic distributed relaxation times, on which the type of cultivation obviously shows no influence but which can be influenced exclusively by post-modifications. Our methodology enables for the first time a clear identification of those parameters which represent a significant factor of influence to the viscoelastic material behaviour, which should enable a more targeted and application-relevant development of BNC composites in the future.
CRIS-Team WoS Importer:2021-12-03

Bacterial nanocellulose: The future of controlled drug delivery? - Poetzinger, Yvette; Kralisch, Dana; Fischer, Dagmar (Therapeutic Delivery, 2017)
Although bacterial nanocellulose (BNC), a natural nanostructured biopolymer network, offers unique material characteristics, the number of drug-loaded BNC-based carriers in clinical trials or on the market is still low. This report provides an overview of aspects still limiting the broad application of BNC as drug-delivery system and the challenges for its future applications. Continuous large-scale production, storability, the loading and controlled release of critical drugs, for example, with high molar mass or highly lipophilic character as well as the formulation of long-term release systems will be highlighted. Recent achievements toward promoting the application of BNC as drug-delivery system and overcoming these obstacles will be discussed.
CRIS-Team Scopus Importer:2020-10-13
Keywords: bacterial nanocellulose; controlled release; drug delivery; production; storage

Bacterial nanocellulose with a shape-memory effect as potential drug delivery system - Mueller, Astrid; Zink, Matthias; Hessler, Nadine; Wesarg, Falko; Mueller, Frank A.; Kralisch, Dana; Fischer, Dagmar (RSC Advances, 2014)
In the steadily emerging field of applications for the natural biopolymer bacterial nanocellulose (BNC), the development of environmentally-friendly and cost-saving techniques to form xerogels by partial or complete dewatering is of great interest for convenient storage, handling and a reduced risk of microbial contamination. Air-dried BNC itself is not able to rehydrate after complete drying due to a structural collapse. In the present paper, it was supplemented with different hydrophilic, water-binding additives and characterized regarding morphology, re-swelling behavior, mechanical stability and potential as drug delivery system. A fast rehydration could be obtained by the addition of magnesium chloride > glucose > sucrose > sorbitol, with a maximum re-swelling percentage up to about 88% (magnesium chloride) of the initial wet weight. In contrast, poly(ethylene glycol) (8 kDa), lactose and trehalose reached only 12-30% whereas mannitol and sodium chloride only had a negligible effect. A high re-swelling value was found to be correlated with the preservation of the three-dimensional BNC network structure and mechanical characteristics such as compression and tensile strength. Confirming the relevance of these findings, the use of the hydrophilic model drug azorubine demonstrated the applicability of the shapememorized bacterial nanocellulose as drug delivery system with controllable release profiles.
CRIS-Team Scopus Importer:2020-10-13

Bakterien helfen heilen - Bakterielle Nanocellulose als Arzneistoffträgersystem - Fischer, Dagmar; Kralisch, Dana (Deutsche Apotheker Zeitung, 2012)
CRIS-Team Scopus Importer:2020-10-13

Beneficial modulation of lipid mediator biosynthesis in innate immune cells by antirheumatic tripterygium wilfordii glycosides - Zhang, Kehong; Pace, Simona; Jordan, Paul M.; Peltner, Lukas K.; Weber, Alexander Christian; Fischer, Dagmar; Hofstetter, Robert K.; Chen, Xinchun; Werz, Oliver (Biomolecules, 2021)
Tripterygium wilfordii glycosides (TWG) is a traditional Chinese medicine with effectiveness against rheumatoid arthritis (RA), supported by numerous clinical trials. Lipid mediators (LM) are biomolecules produced from polyunsaturated fatty acids mainly by cyclooxygenases (COX) and lipoxygenases (LOX) in complex networks which regulate inflammation and immune responses and are strongly linked to RA. The mechanism by which TWG affects LM networks in RA treatment remains elusive. Employing LM metabololipidomics using ultra-performance liquid chromatog-raphy-tandem mass spectrometry revealed striking modulation of LM pathways by TWG in human monocyte-derived macrophage (MDM) phenotypes. In inflammatory M1-MDM, TWG (30 µg/mL) potently suppressed agonist-induced formation of 5-LOX products which was confirmed in human PMNL and traced back to direct inhibition of 5-LOX (IC50 = 2.9 µg/mL). TWG also efficiently blocked thromboxane formation in M1-MDM without inhibiting other prostanoids and COX enzymes. Im-portantly, in anti-inflammatory M2-MDM, TWG (30 µg/mL) induced pronounced formation of specialized pro-resolving mediators (SPM) and related 12/15-LOX-derived SPM precursors, without COX and 5-LOX activation. During MDM polarization, TWG (1 µg/mL) decreased the capacity to generate pro-inflammatory 5-LOX and COX products, cytokines and markers for M1 phenotypes. Together, suppression of pro-inflammatory LM but SPM induction may contribute to the antirheu-matic properties of TWG.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Cyclooxygenase; Inflammation; Lipoxygenase; Specialized pro-resolving mediators; Tripterygium wilfordii glycosides

Branched and linear poly(ethylene imine)-based conjugates: Synthetic modification, characterization, and application - Jaeger, Michael; Schubert, Stephanie; Ochrimenko, Sofia; Fischer, Dagmar; Schubert, Ulrich S. (Chemical Society Reviews, 2012)
Poly(ethylene imine)s (PEIs) are widely used in different applications, but most extensively investigated as non-viral vector systems. The high ability of cationic PEIs to complex and condense negatively charged DNA and RNA combined with their inherent proton sponge behavior accounts for the excellent efficiency in gene delivery. Further chemical modifications of the polymer expand the application potential, primarily aiming at increased transfection efficiency, cell selectivity and reduced cytotoxicity. Improvements in the synthesis of tailor-made PEIs in combination with new in-depth analytical techniques offer the possibility to produce highly purified polymers with defined structures. The contemporary strategies towards linear and branched poly(ethylene imine)s with modified surface characteristics, PEI-based copolymers as well as conjugates with bioactive molecules will be discussed. In this regard, the versatile branched PEIs have been successfully modified in a statistical manner, whereas the linear counterparts open avenues to design and synthesize well-defined architectures, in order to exploit their high potential in gene delivery. © 2012 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2020-10-13

Breaking the biofilm barrier: The role of stabilizers in biofilm penetration and pulmonary antibiotic delivery by polymer nanoparticles - Ernst, Julia; Klinger-Strobel, Mareike; Thamm, Jana; Makarewicz, Oliwia; Pletz, Mathias W.; Fischer, Dagmar (Pharmazeutische Industrie, 2019)
In infectious lung diseases, poly(lactide-co-glycolide) (PLGA) nanoparticles are highly advancing for drug delivery in respiratory tract infections due to their ability to overcome biological barriers such as bacterial lung biofilms and human mucus. As the selection of stabilizers used during the formulation of nanoparticles affects their surface properties, this study aimed to test different polymers for their capability to stabilize PLGA particles and their influence on biofilm and mucus penetration. Polyvinyl alcohol (PVA), chitosan (Cs), poloxamer 188 (P188), and poly(ethylene glycol) (PEG) were selected to prepare fluorescently labeled spherical nanoparticles of 550-800 nm using an emulsion-diffusion-evaporation technique. In an artificial mucus system particle permeation was found to increase depending on particle size and stabilizer type with P188 < PVA < PEG < Cs. In vitro penetration of biofilms of Burkholderia cepacia and Staphylococcus aureus gave comparable results. The covalent binding of PEG to PLGA improved the penetration ability in all assays and as proof of concept demonstrated the highly efficient bacterial killing of biofilm-embedded B. cepacia after tobramycin encapsulation compared to free drug.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biofilm; Burkholderia cepacia; Nanoparticle; Stabilizer; Staphylococcus aureus; Tobramycin

Bromo-substituted indirubins for inhibition of protein kinase-mediated signalling involved in inflammatory mediator release in human monocytes - Bachmann, Vivien; Schädel, Patrick; Westhoff, Jan; Perić, Milica; Schömberg, Fritz; Skaltsounis, Alexios Leandros; Höppener, Stephanie; Pantsar, Tatu; Fischer, Dagmar; Vilotijević, Ivan; Werz, Oliver (Bioorganic Chemistry, 2024)
Targeting protein kinases that regulate signalling pathways in inflammation is an effective pharmacological approach to alleviate uncontrolled inflammatory diseases. In this context, the natural product indirubin and its 6-bromo-substituted analogue 6-bromoindirubin-3 -glycerol-oxime ether (6BIGOE; 1) were identified as potent inhibitors of glycogen synthase kinase-3β (GSK-3β). These inhibitors suppress the release of pro-inflammatory cytokines and prostaglandins (PG) from human monocytes. However, indirubin derivatives target several protein kinases such as cyclin-dependent kinases (CDKs) which has been a major concern for their application in inflammation therapy. Here, we report on a library of 13 5-bromo-substituted indirubin derivatives that have been designed to improve potency and target selectivity. Side-by-side comparison of reference compound 1 (6BIGOE) with 5-bromo derivatives revealed its isomer 2 (5BIGOE), as the most potent derivative able to supress pro-inflammatory cytokine and PG release in lipopolysaccharide-stimulated human monocytes. Analysis of protein kinase inhibition in intact monocytes, supported by our in silico findings, proposed higher selectivity of 1 for GSK-3β inhibition with lesser potency against CDKs 8 and 9. In contrast, 2 supressed the activity of these CDKs with higher effectiveness than GSK-3β, representing additional targets of indirubins within the inflammatory response. Encapsulation of 1 and 2 into polymer-based nanoparticles (NP) improved their pharmacological potential. In conclusion, the 5- and 6-brominated indirubins 1 and 2 as dual GSK-3β and CDK8/9 inhibitors represent a novel concept for intervention with inflammatory disorders.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Bromoindirubins; Cyclin-dependent kinases; Cytokines; Glycogen synthase kinase-3β; Inflammation; Monocytes; Polymer-based nanoparticles; Prostaglandins

Comprehensive analysis of the in vitro and ex ovo hemocompatibility of surface engineered iron oxide nanoparticles for biomedical applications - Schlenk, Florian; Werner, Sebastian; Rabel, Martin; Jacobs, Franziska; Bergemann, Christian; Clement, Joachim H.; Fischer, Dagmar (Archives of Toxicology, 2017)
A set of biomedically relevant iron oxide nanoparticles with systematically modified polymer surfaces was investigated regarding their interaction with the first contact partners after systemic administration such as blood cells, blood proteins, and the endothelial blood vessels, to establish structure–activity relationships. All nanoparticles were intensively characterized regarding their physicochemical parameters. Cyto- and hemocompatibility tests showed that (1) the properties of the core material itself were not relevant in short-term incubation studies, and (2) toxicities increased with higher polymer mass, neutral = anionic < cationic surface charge and charge density, as well as agglomeration. Based on this, it was possible to classify the nanoparticles in three groups, to establish structure–activity relationships and to predict nanosafety. While the results between cyto- and hemotoxicity tests correlated well for the polymers, data were not fully transferable for the nanoparticles, especially in case of cationic low molar mass polymer coatings. To evaluate the prediction efficacy of the static in vitro models, the results were compared to those obtained in an ex ovo shell-less hen’s egg test after microinjection under dynamic flow conditions. While the polymers demonstrated hemotoxicity profiles comparable to the in vitro tests, the size-dependent risks of nanoparticles could be more efficiently simulated in the more complex ex ovo environment, making the shell-less egg model an efficient alternative to animal studies according to the 3R concept.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Blood compatibility; Hen’s egg; Magnetic nanoparticles; Nanosafety; Protein corona

Controlled modulation of serum protein binding and biodistribution of asymmetric cyanine dyes by variation of the number of sulfonate groups - Hamann, Franziska M.; Brehm, Robert; Pauli, Jutta; Grabolle, Markus; Frank, Wilhelm; Kaiser, Werner A.; Fischer, Dagmar; Resch-Genger, Ute; Hilger, Ingrid (Molecular Imaging, 2011)
To assess the suitability of asymmetric cyanine dyes for in vivo fluoro-optical molecular imaging, a comprehensive study on the influence of the number of negatively charged sulfonate groups governing the hydrophilicity of the DY-67x family of asymmetric cyanines was performed. Special attention was devoted to the plasma protein binding capacity and related pharmacokinetic properties. Four members of the DY-67x cyanine family composed of the same main chromophore, but substituted with a sequentially increasing number of sulfonate groups (n 5 1-4; DY-675, DY-676, DY-677, DY-678, respectively), were incubated with plasma proteins dissolved in phosphate-buffered saline. Protein binding was assessed by absorption spectroscopy, gel electrophoresis, ultrafiltration, and dialysis. Distribution of dye in organs was studied by intraveneous injection of 62 nmol dye/kg body weight into mice (n 5 12; up to 180 minutes postinjection) using whole-body near-infrared fluorescence imaging. Spectroscopic studies, gel electrophoresis, and dialysis demonstrated reduced protein binding with increasing number of sulfonate groups. The bovine serum albumin binding constant of the most hydrophobic dye, DY-675, is 18 times higher than that of the most hydrophilic fluorophore, DY-678. In vivo biodistribution analysis underlined a considerable influence of dye hydrophilicity on biodistribution and excretion pathways, with the more hydrophobic dyes, DY-675 and DY-676, accumulating in the liver, followed by strong fluorescence signals in bile and gut owing to accumulation in feces and comparatively hydrophilic DY-678-COOH accumulating in the bladder. Our results demonstrate the possibility of selectively controlling dye-protein interactions and, thus, biodistribution and excretion pathways via proper choice of the fluorophore's substitution pattern. This underlines the importance of structure-property relationships for fluorescent labels. Moreover, our data could provide the basis for the rationalization of future contrast agent developments. © 2011 Decker Publishing.
CRIS-Team Scopus Importer:2020-10-13

Controlled release of the α-tocopherol-derived metabolite α-13′-carboxychromanol from bacterial nanocellulose wound cover improves wound healing - Hoff, Jessica; Karl, Berit; Gerstmeier, Jana; Beekmann, Uwe; Schmölz, Lisa; Börner, Friedemann; Kralisch, Dana; Bauer, Michael; Werz, Oliver; Fischer, Dagmar; Lorkowski, Stefan; Press, Adrian T. (Nanomaterials, 2021)
Inflammation is a hallmark of tissue remodeling during wound healing. The inflammatory response to wounds is tightly controlled and well-coordinated; dysregulation compromises wound healing and causes persistent inflammation. Topical application of natural anti-inflammatory products may improve wound healing, in particular under chronic pathological conditions. The long-chain metabolites of vitamin E (LCM) are bioactive molecules that mediate cellular effects via oxidative stress signaling as well as anti-inflammatory pathways. However, the effect of LCM on wound healing has not been investigated. We administered the α-tocopherol-derived LCMs α-13′-hydroxychromanol (α-13′-OH) and α-13′-carboxychromanol (α-13′-COOH) as well as the natural product garcinoic acid, a δ-tocotrienol derivative, in different pharmaceutical formulations directly to wounds using a splinted wound mouse model to investigate their effects on the wounds’ proinflammatory microenvironment and wound healing. Garcinoic acid and, in particular, α-13′-COOH accelerated wound healing and quality of the newly formed tissue. We next loaded bacterial nanocellulose (BNC), a valuable nanomaterial used as a wound dressing with high potential for drug delivery, with α-13′-COOH. The controlled release of α-13′-COOH using BNC promoted wound healing and wound closure, mainly when a diabetic condition was induced before the injury. This study highlights the potential of α-13′-COOH combined with BNC as a potential active wound dressing for the advanced therapy of skin injuries.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Biocompatible nanocellulose; Controlled release; Drug delivery; Inflammation; Natural products; Tocopherols; Wound healing

Development and characterization of bacterial nanocellulose loaded with Boswellia serrata extract containing nanoemulsions as natural dressing for skin diseases - Karl, Berit; Alkhatib, Yaser; Beekmann, Uwe; Bellmann, Tom; Blume, Gabriele; Steiniger, Frank; Thamm, Jana; Werz, Oliver; Kralisch, Dana; Fischer, Dagmar (International Journal of Pharmaceutics, 2020)
The combination of the anti-inflammatory lipophilic Boswellia serrata extract with the natural hydropolymer bacterial nanocellulose (BNC) for the treatment of skin diseases is counteracted by their different hydro/lipophilicity. To overcome the hydrophilicity of the BNC, the water in its network was exchanged by single and double nanoemulsions. Incorporation of the Boswellia serrata extract in the nanoemulsions formed particles of about 115 to 150 nm with negative zeta potential and storage stability over 30 days at temperatures between 4 and 32 °C. Their loading into the BNC did not change the preferential characteristics of the nanocellulose like water absorption and retention, softness, and pressure stability in a relevant way. Loaded BNC could be sterilized by an electron-beam procedure. A biphasic drug release profile of lead compounds was observed by Franz cell diffusion test. The biocompatibility of the loaded BNC was confirmed ex ovo by a shell-less hen's egg test. Tape stripping experiments using porcine skin determined a dependency of the drug penetration into skin on the type of nanoemulsion, single vs. repeated applications and the incubation time. In conclusion, the hydrophilicity of BNC could be overcome using nanoemulsions which offers the possibility for the anti-inflammatory skin treatment with Boswellia serrata extract.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial nanocellulose; Boswellia serrata; Drug delivery; Inflammation; Nanoemulsion; Skin

Dextran-graft-linear poly(ethylene imine)s for gene delivery: Importance of the linking strategy - Ochrimenko, Sofia; Vollrath, Antje; Tauhardt, Lutz; Kempe, Kristian; Schubert, Stephanie; Schubert, Ulrich S.; Fischer, Dagmar (Carbohydrate Polymers, 2014)
Low molar mass linear poly(ethylene imine)s (lPEI) were grafted onto dextran via different synthesis routes aiming at the elucidation of structure-property relationships of dextran-graft-linear poly(ethylene imine) (dex-g-lPEI) conjugates for gene delivery applications. Beside the molar mass of well-defined lPEIs and the linker unit, also the amount of lPEI in the polymeric vectors was varied. The synthesized dextran modifications were characterized regarding their chemical structure and showed enhanced complexation and stabilization of DNA against enzymatic degradation. The transfection efficiency of dex-g-lPEIs was increased compared to unmodified lPEI and revealed a dependency of the used linking strategy. All complexes of DNA and dex-g-lPEIs were found to be nontoxic, but the synthesis route showed a strong influence on the aggregation of red blood cells. In conclusion, the linking strategy of lPEI to dextran has a significant impact on the physicochemical characteristics of DNA/polymer complexes, the biocompatibility as well as the transfection efficiency. © 2014 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biocompatibility; Cationized dextran; Gene delivery; Poly(ethylene imine); Structure-property relationship

Distinct endocytosis and immune activation of poly lactic-co-glycolic acid nanoparticles prepared by single- and double-emulsion evaporation - Spiecker, Erdmann; Hackstein, Holger; Wu, Mingjian; Scheuer, Karl; Brox, Regine; Apeleo Zubiri, Benjamin; Pusch, Lennart; Jandt, Klaus D.; Yokosawa, Tadahiro; Fischer, Dagmar (2021)
Background: Poly lactic-co-glycolic acid (PLGA) nanoparticles can be prepared by emulsion-solvent-evaporation from o/w and w(1)/o/w(2) emulsions. Aims: To elaborate similarities and differences regarding mechanical, morphological and physicochemical properties, as well as endocytosis and dose-dependent immune responses by primary human leukocytes between nanoparticles prepared by these two methods. Methods: Fluorescently labeled as well as TLR-agonist (R848)-loaded PLGA nanoparticles were prepared via both single- and double-emulsion solvent evaporation. Results: Particles prepared by both methods were similar in chemical composition and surface charge but exhibited slight differences in size and morphology. Pronounced differences were found for loading, dissolution and mechanical properties. The particles were differently endocytosed by monocytes and induced qualitatively and quantitatively different immune responses. Conclusions: Variations in nanoparticle preparation can affect particle-derived immunological characteristics.
CRIS-Team WoS Importer:2021-09-24

Drug delivery of 6-bromoindirubin-3’-glycerol-oxime ether employing poly(d,l-lactide-co-glycolide)-based nanoencapsulation techniques with sustainable solvents - Czapka, Anna; Grune, Christian; Schaedel, Patrick; Bachmann, Vivien; Scheuer, Karl; Dirauf, Michael; Weber, Christine; Skaltsounis, Alexios-Leandros; Jandt, Klaus D.; Schubert, Ulrich S.; Fischer, Dagmar; Werz, Oliver (Journal of Nanobiotechnology, 2022)
Background: Insufficient solubility and stability of bioactive small molecules as well as poor biocompatibility may cause low bioavailability and are common obstacles in drug development. One example of such problematic molecules is 6-bromoindirubin-3'-glycerol-oxime ether (6BIGOE), a hydrophobic indirubin derivative. 6BIGOE potently modulates the release of inflammatory cytokines and lipid mediators from isolated human monocytes through inhibition of glycogen synthase kinase-3 in a favorable fashion. However, 6BIGOE suffers from poor solubility and short half-lives in biological aqueous environment and exerts cytotoxic effects in various mammalian cells. In order to overcome the poor water solubility, instability and cytotoxicity of 6BIGOE, we applied encapsulation into poly(d,l-lactide-co-glycolide) (PLGA)-based nanoparticles by employing formulation methods using the sustainable solvents Cyrene™ or 400 g/mol poly(ethylene glycol) as suitable technology for efficient drug delivery of 6BIGOE. Results: For all preparation techniques the physicochemical characterization of 6BIGOE-loaded nanoparticles revealed comparable crystallinity, sizes of about 230 nm with low polydispersity, negative zeta potentials around − 15 to − 25 mV, and biphasic release profiles over up to 24 h. Nanoparticles with improved cellular uptake and the ability to mask cytotoxic effects of 6BIGOE were obtained as shown in human monocytes over 48 h as well as in a shell-less hen’s egg model. Intriguingly, encapsulation into these nanoparticles fully retains the anti-inflammatory properties of 6BIGOE, that is, favorable modulation of the release of inflammation-relevant cytokines and lipid mediators from human monocytes. Conclusions: Our formulation method of PLGA-based nanoparticles by applying sustainable, non-toxic solvents is a feasible nanotechnology that circumvents the poor bioavailability and biocompatibility of the cargo 6BIGOE. This technology yields favorable drug delivery systems for efficient interference with inflammatory processes, with improved pharmacotherapeutic potential. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-01-14
Keywords: Drug delivery; Indirubin; Inflammation; Nanoparticles; PLGA; Sustainable solvents

Drug delivery strategies in the therapy of inflammatory bowel disease - Lautenschlaeger, Christian; Schmidt, Carsten; Fischer, Dagmar; Stallmach, Andreas (Advanced Drug Delivery Reviews, 2014)
Inflammatory bowel disease (IBD) is a frequently occurring disease in young people, which is characterized by a chronic inflammation of the gastrointestinal tract. The therapy of IBD is dominated by the administration of anti-inflammatory and immunosuppressive drugs, which suppress the intestinal inflammatory burden and improve the disease-related symptoms. Established treatment strategies are characterized by a limited therapeutical efficacy and the occurrence of adverse drug reactions. Thus, the development of novel disease-targeted drug delivery strategies is intended for a more effective therapy and demonstrates the potential to address unmet medical needs. This review gives an overview about the established as well as future-oriented drug targeting strategies, including intestine targeting by conventional drug delivery systems (DDS), disease targeted drug delivery by synthetic DDS and disease targeted drug delivery by biological DDS. Furthermore, this review analyses the targeting mechanisms of the respective DDS and discusses the possible field of utilization in IBD. © 2014 Elsevier B.V.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biological drug delivery systems; Colitis ulcerosa; Crohn's disease; Drug targeting; Inflammatory bowel disease; Particular drug delivery systems; Targeted drug delivery

Electrophotographic Powder Application for Surface Functionalization of Polymer Parts with Thin Silver‐Nanoadditivated Bactericidal Layers - Kricke, Jan Lino; Ebert, Niklas; Sorarrain, Ane; Roth, Stephan; Fischer, Dagmar; Schmidt, Michael; Gökce, Bilal; Marimón, José María; Kopp, Sebastian-Paul; Doñate‐Buendía, Carlos (Advanced Materials Technologies, 2025)
The feedstock in laser beam powder bed fusion of plastics (PBF-LB/P) is typically limited to a few materials with strict flowability requirements and low recycling rates, compromising its economic efficiency and sustainability. Polymer nanoadditivation gains attraction to tailor their physiochemical properties by incorporating nanoadditives. Herein, a new approach is introduced to functionalize polymer part surfaces via electrophotographic powder application (EPA). Polyamide 12 (PA 12) microparticles decorated with laser-synthesized silver nanoparticles (Ag NPs) are printed as thin layers on bulk PA 12 parts. The coating provides bactericidal functionality to the printed part with reduced nanoadditive employment. Indeed, only two Ag-PA 12 layers accounting for a 140 µm thick coating inhibit S. aureus and E. coli bacteria growth. As a result of the low coating thickness and Ag NP loading of only 0.1 wt.%, the mechanical and calorimetric properties remain unaffected. Owing to its versatility, the proposed approach is envisioned to facilitate selective surface functionalization toward graded materials printing at reduced costs and waste generatio

Elucidating preparation-structure relationships for the morphology evolution during the RAFT dispersion polymerization of: N -acryloyl thiomorpholine - Sobotta, Fabian H.; Kuchenbrod, Maren T.; Grune, Christian; Fischer, Dagmar; Hoeppener, Stephanie; Brendel, Johannes C. (Polymer Chemistry, 2021)
Polymerization-induced self-assembly (PISA) is an emerging methodology for the in situ preparation of complex polymeric nanostructures in aqueous solution. However, the scope of monomers allowing morphology transitions remains limited, which is related to the low solubility of many monomers in water. Morphology transitions have therefore been restricted to more hydrophilic monomers necessitating rather long hydrophobic blocks to induce aggregation. Even longer ones are required to induce the changes of the morphology deviating from a spherical shape-a fact that limits the accessible hydrophobic domain sizes or morphologies. Here, we demonstrate that N-acryloyl thiomorpholine (NAT) represents a unique monomer which is fully miscible with water, but results in hydrophobic polymers at degrees of polymerization (DP) below 10, while morphology transitions can occur at DPs of 25 and even less. Synthesizing over 70 block copolymers in total we identified key parameters, such as hydrophilic block length, temperature, ratio of co-solvent, and concentration, influencing the self-assembly process. While the high glass transition temperature (Tg) of PNAT may cause frozen and kinetically trapped micellar cores, suitable synthesis conditions enable access to all common morphologies including spheres, worms, and vesicles as well as intermediate phases. Applying this technique, various nanostructures are reproducibly formed in situ in aqueous dispersions rendering the presented PISA system a highly versatile, new route to functional block copolymer nanostructures for various applications. This journal is
CRIS-Team Scopus Importer:2021-04-02

Encapsulation of the Anti-inflammatory Dual FLAP/sEH Inhibitor Diflapolin Improves the Efficiency in Human Whole Blood - Grune, Christian; Kretzer, Christian; Zergiebel, Stephanie; Kattner, Sven; Thamm, Jana; Hoeppener, Stephanie; Werz, Oliver; Fischer, Dagmar (Journal of Pharmaceutical Sciences, 2022)
Diflapolin is a dual FLAP/sEH inhibitor with potent anti-inflammatory efficiency in cellular assays and experimental in vivo studies. Despite these outstanding characteristics, its high lipophilicity and plasma protein binding hamper the bioactivity in blood. To overcome these limitations, diflapolin was encapsulated in poly (lactic-co-glycolic acid) nanoparticles to develop an efficient and biocompatible drug delivery system. Two different cosolvent approaches were tested showing the possibility to exchange dimethyl sulfoxide in the organic phase by the sustainable 400 g/mol poly(ethylene glycol). A particle size of 220 nm and the amorphous encapsulation of diflapolin in high amounts rendered the nanoparticles appropriate for the intended application. Excellent biocompatibility of the nanoparticles was demonstrated in an ex ovo hen's egg model. The potent suppression of FLAP-dependent 5-lipoxygenase product formation by the nanoparticles in human whole blood, superior to the free drug, makes them to a promising drug delivery system to improve the bioactivity of diflapolin.(c) 2021 American Pharmacists Association. Published by Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2022-06-24

Estimating extra length of stay due to healthcare-associated infections before and after implementation of a hospital-wide infection control program - Arefian, Habibollah; Hagel, Stefan; Fischer, Dagmar; Scherag, Andre; Brunkhorst, Frank Martin; Maschmann, Jens; Hartmann, Michael (PLoS ONE, 2019)
Introduction Healthcare-associated infections (HAIs) are a major health concern and have substantial effects on morbidity and mortality and increase healthcare costs. We investigated the effect of a hospital-wide program for the prevention of HAIs on additional length of stay (LOS). Methods We analyzed data from a prospective, single-center, quasi-experimental study with two surveillance periods before and after implementation of an infection prevention intervention program. HAI diagnosis was made according to surveillance definition criteria established by the US Centers for Disease Control and Prevention. A multistate model was used to estimate additional LOS for patients with HAI in both surveillance periods. Results During the first and second periods, 1,568 and 2,336 HAIs were identified among 26,943 and 35,211 patients, respectively. For HAI patients exclusively treated in a general ward, additional LOS was 8.4 (95% confidence interval, CI: 6.8-10.0) days in the first period and 9.6 (95% CI: 8.3-11.0) days in the second period (p = 0.26). For HAI patients treated in both an intensive care unit (ICU) and a general ward, additional LOS was 8.1 (95% CI: 6.3-9.9) days in the first period to 7.3 (95% CI: 6.1-8.5) days in the second period (p = 0.47). Conclusions Healthcare-associated infections prolong LOS. A hospital-wide infection control program did not alter the prolongation of LOS.
CRIS-Team Scopus Importer:2020-10-13

Exploring bacterial cellulose as an engineered living and programmable biomaterial across disciplines through qualitative thematic analysis - Quijano, Luis; Fischer, Dagmar; Ferrero-Regis, Tiziana; Navone, Laura (Scientific Reports, 2025)
Bacterial cellulose is an engineered living material which holds significant potential due to its material properties and broad applicability across scientific and design disciplines. However, challenges in interdisciplinary collaboration, scalability and commercialization have slowed its widespread adoption and integration into industry applications such as fashion and textiles. This study addresses the gap in understanding how bacterial cellulose is perceived, developed, and utilized across scientific and design disciplines. Through 20 semi-structured interviews with scientists and designers around the world, this paper explores the following themes: (1) the human-living material relationship spectrum, which highlights the distinct ways science and design stakeholders interact with bacterial cellulose as a living material; (2) perceptions of a living material made from bacteria; and (3) bacterial cellulose’s potential as a programmable biomaterial. Additionally, we employ Bruno Latour’s Actor-Network Theory to map the complex network of human and non-human actors shaping bacterial cellulose’s trajectory, identifying critical factors such as consumer acceptance, interdisciplinary collaboration, and material culture. By bridging perspectives from science and design, this study offers actionable insights into bacterial cellulose’s future as a sustainable and programmable engineered living material, guiding its responsible development and broader adoption across industries.
CRIS-Team Scopus Importer:2025-05-30

FAU Forschungszentrum Neue Wirkstoffe (FAU NeW) nimmt Arbeit auf - interdisziplinäre Zusammenarbeit zur Entwicklung neuer Wirkstoffe - Pischetsrieder, Monika; Fischer, Dagmar (Deutsche Lebensmittel-Rundschau, 2023)
CRIS-Team Scopus Importer:2024-12-16

Fungal Biosurfactants from Mortierella alpina - Baldeweg, Florian; Warncke, Paul; Fischer, Dagmar; Gressler, Markus (Organic Letters, 2019)
The zygomycete Mortierella alpina is a well-known producer of polyunsaturated fatty acids in the food industry. Two series of its secondary metabolites are reported: Malpinins, a family of amphiphilic acetylated hexapeptides, were chemically characterized and serve as natural emulsifiers during lipid secretion. Additionally, hydrophobic cyclopentapeptides, malpibaldins, were structurally elucidated by NMR experiments, and their absolute stereochemistry was elucidated through chemical derivatization and synthesis. This work highlights lower fungi as a novel reservoir for natural products.
CRIS-Team Scopus Importer:2020-10-13

Harnessing Guanidinium and Imidazole Functional Groups: A Dual-Charged Polymer Strategy for Enhanced Gene Delivery - Mapfumo, Prosper P.; Reichel, Liên S.; Leer, Katharina; Egger, Jan; Dzierza, Andreas; Peneva, Kalina; Fischer, Dagmar; Traeger, Anja (ACS Macro Letters, 2024)
Histidine and arginine are two amino acids that exhibit beneficial properties for gene delivery. In particular, the imidazole group of histidine facilitates endosomal release, while the guanidinium group of arginine promotes cellular entry. Consequently, a dual-charged copolymer library based on these amino acids was synthesized via reversible addition-fragmentation chain transfer (RAFT) polymerization. The content of the N-acryloyl-l-histidine (His) monomer was systematically increased, while maintaining consistent levels of methyl N-acryloyl-l-argininate hydrochloride (ArgOMe) or N-(4-guanidinobutyl)acrylamide hydrochloride (GBAm). The resulting polymers formed stable, nanosized polyplexes when complexed with nucleic acids. Remarkably, candidates with increased His content exhibited reduced cytotoxicity profiles and enhanced transfection efficiency, particularly retaining this performance level at lower pDNA concentrations. Furthermore, endosomal release studies revealed that increased His content improved endosomal release, while ArgOMe improved cellular entry. These findings underscore the potential of customized dual-charged copolymers and the synergistic effects of His and ArgOMe/GBAm in enhancing gene delivery.
CRIS-Team Scopus Importer:2024-08-02

Hospital-related cost of sepsis: A systematic review - Arefian, Habibollah; Heublein, Steffen; Scherag, Andre; Brunkhorst, Frank Martin; Younis, Mustafa Z.; Moerer, Onnen; Fischer, Dagmar; Hartmann, Michael (Journal of Infection, 2017)
Objectives This article systematically reviews research on the costs of sepsis and, as a secondary aim, evaluates the quality of economic evaluations reported in peer-reviewed journals. Methods We systematically searched the MEDLINE, National Health Service (Abstracts of Reviews of Effects, Economic Evaluation and Health Technology Assessment), Cost-effectiveness Analysis Registry and Web of Knowledge databases for studies published between January 2005 and June 2015. We selected original articles that provided cost and cost-effectiveness analyses, defined sepsis and described their cost calculation method. Only studies that considered index admissions and re-admissions in the first 30 days were published in peer-reviewed journals and used standard treatments were considered. All costs were adjusted to 2014 US dollars. Medians and interquartile ranges (IQRs) for various costs of sepsis were calculated. The quality of economic studies was assessed using the Drummond 10-item checklist. Results Overall, 37 studies met our eligibility criteria. The median of the mean hospital-wide cost of sepsis per patient was 32,421 (IQR 20,745–40,835), and the median of the mean ICU cost of sepsis per patient was 27,461 (IQR 16,007–31,251). Overall, the quality of economic studies was low. Conclusions Estimates of the hospital-related costs of sepsis varied considerably across the included studies depending on the method used for cost calculation, the type of sepsis and the population that was examined. A standard model for conducting cost improve the quality of studies on the costs of sepsis.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Cost; Sepsis; Septic shock; Septicemia; Severe sepsis

Immobilization of plasmids in bacterial nanocellulose as gene activated matrix - Poetzinger, Yvette; Rahnfeld, Lisa; Kralisch, Dana; Fischer, Dagmar (Carbohydrate Polymers, 2019)
The synergy of the local delivery of nucleic acids using a hydrogel-based gene activated matrix (GAM) might support regenerative processes on a genetic level by concurrently providing a cell-friendly microenvironment. To investigate bacterial nanocellulose (BNC) as GAM, two plasmids (pSV-β-Gal and pGL3) were incorporated by reswelling and injection techniques forming matrix and core-shell systems as determined by SEM and staining experiments. The release was found to be dependent on the type of BNC, the plasmid and the loading technique, and lasted over at least 20 days. No morphological or mechanical changes of the BNC due to the presence of plasmids were observed. Immobilized plasmids especially in the matrix systems were protected against enzymatic degradation by maintaining the high biocompatibility of BNC and transfection efficacy of the plasmids. These results indicate that BNC can be used as a promising and renewable carrier for the application as local gene delivery system.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial nanocellulose; Biocompatibility; Controlled release; Gene activated matrix; Gene delivery

Improving colloidal stability of silica nanoparticles when stored in responsive gel: application and toxicity study - Giovannini, Giorgia; Warncke, Paul; Fischer, Dagmar; Stranik, Ondrej; Hall, Andrew J.; Gubala, Vladimir (Nanotoxicology, 2018)
When silica nanoparticles (SiNP) are stored in aqueous solution, even for few hours, they have a tendency to form agglomerates and therefore adapt inhomogeneous structures. Here we present a very practical method to store SiNP in responsive hydrogel. We have confirmed that SiNP kept in the responsive hydrogel do not undergo through undesirable morphological changes and while in storage they maintain their excellent colloidal stability. The effect of SiNP hollowing (i.e. dissolution of the core of the particles that leaves empty cavity inside) was significantly inhibited in the hydrogel, which is a critical feature for any nano-medical applications (e.g. controlled drug release). To demonstrate the applicability of the hydrogel-storing concept within a biologically relevant context, in this work we have evaluated the toxicological effects of the responsive SiNP-gel formulation in a model in vitro (human cell line U87GM and hemocompatibility using red blood cells) and ex ovo (hen’s egg test) experiments. Particles stored in the gel as well as the pure gel did not affect the hemocompatibility (hemolysis and erythrocyte aggregation) up to a concentration of 100 µg/mL. Furthermore, systemic injections into the blood circulation of the chick area vasculosa confirmed the biocompatibility in a more complex biological environment. All evaluated toxicological values (hemorrhage, thrombosis, vascular lysis, and lethality) were comparable with the negative control, and no differences in toxicological response could be observed between the SiNP stored in hydrogel and the control nanoparticles stored in the solution.
CRIS-Team Scopus Importer:2020-10-13
Keywords: hemotoxicity; hen’ egg test; hydrogel; Nanoparticles; stability; storage; toxicity

Incorporation of Indole Significantly Improves the Transfection Efficiency of Guanidinium-Containing Poly(Methacrylamide)s - Cokca, Ceren; Zartner, Leon; Tabujew, Ilja; Fischer, Dagmar; Peneva, Kalina (Macromolecular Rapid Communications, 2020)
A highly efficient transfection agent is reported that is based on terpolymer consisting of N-(2-hydroxypropyl)methacrylamide (HPMA), N-(3-guanidinopropyl) methacrylamide (GPMA), and N-(2-indolethyl)methacrylamide monomers (IEMA) by analogy to the amphipathic cell-penetrating peptides containing tryptophan and arginine residues. The incorporation of the indole-bearing monomer leads to successful plasmid DNA condensation even at a nitrogen-to-phosphate (N/P) ratio of 1. The hydrodynamic diameter of polyplexes is determined to be below 200 nm for all N/P ratios. The transfection studies demonstrate a 200-fold increase of the transgene expression in comparison to P(HPMA-co-GPMA) with the same guanidinium content. This study reveals the strong potential of the indole group as a side-chain pendant group that can increase the cellular uptake of polymers and the transfection efficiency of the respective polyplexes.
CRIS-Team Scopus Importer:2020-10-13
Keywords: gene delivery; guanidinium; indole; methacrylamide

Innovations in gene therapy Innovationen in der gentherapie - Fischer, Dagmar (Deutsche Apotheker Zeitung, 2011)
CRIS-Team Scopus Importer:2020-10-13

In situ Formation of Polymer Microparticles in Bacterial Nanocellulose Using Alternative and Sustainable Solvents to Incorporate Lipophilic Drugs - Bellmann, Tom; Thamm, Jana; Beekmann, Uwe; Kralisch, Dana; Fischer, Dagmar (Pharmaceutics, 2023)
Bacterial nanocellulose has been widely investigated in drug delivery, but the incorporation of lipophilic drugs and controlling release kinetics still remain a challenge. The inclusion of polymer particles to encapsulate drugs could address both problems but is reported sparely. In the present study, a formulation approach based on in situ precipitation of poly(lactic-co-glycolic acid) within bacterial nanocellulose was developed using and comparing the conventional solvent N-methyl-2-pyrrolidone and the alternative solvents poly(ethylene glycol), CyreneTM and ethyl lactate. Using the best-performing solvents N-methyl-2-pyrrolidone and ethyl lactate, their fast diffusion during phase inversion led to the formation of homogenously distributed polymer microparticles with average diameters between 2.0 and 6.6 µm within the cellulose matrix. Despite polymer inclusion, the water absorption value of the material still remained at 50% of the original value and the material was able to release 32 g/100 cm2 of the bound water. Mechanical characteristics were not impaired compared to the native material. The process was suitable for encapsulating the highly lipophilic drugs cannabidiol and 3-O-acetyl-11-keto-β-boswellic acid and enabled their sustained release with zero order kinetics over up to 10 days. Conclusively, controlled drug release for highly lipophilic compounds within bacterial nanocellulose could be achieved using sustainable solvents for preparation.
CRIS-Team Scopus Importer:2023-03-10
Keywords: bacterial nanocellulose; boswellic acids; cannabidiol; drug delivery; microparticles; PLGA

Investigation of Inertial Cavitation Induced by Modulated Focused Ultrasound Stimuli - George, Benedikt; Savsek, Ula; Fischer, Dagmar; Ermert, Helmut; Rupitsch, Stefan Johann (Current Directions in Biomedical Engineering, 2022)
A passive cavitation detection setup is used to assess and verify the capability of frequency- and amplitude-modulated ultrasound burst signals on the generation of inertial cavitation. The measurements were conducted with a flow-through tissue-mimicking phantom with a canal of dc = 1 mm in diameter simulating a fine blood vessel. By means of a flow velocity of vf = 50 mm/s circulating blood in the cardiovascular system is imitated. Applying signal frequencies from f = 550 − 950 kHz and peak rarefaction pressures in a range from pPRFP ≈ 0.17 − 1.81 MPa, various ultrasound stimuli with alternating signal parameters were investigated in the absence and presence of a talcum-water mixture acting as cavitation nuclei. By evaluating the broadband emissions in the frequency domain and calculating the voltage spectral density Srm, the results can be compared. The findings of the present study demonstrate that each ultrasound stimulus triggers a similar strength of cavitation noise at the same Mechanical Index, representing a certain pressure. Over the whole frequency and Mechanical Index (pressure) range, each ultrasound signal type generates a voltage spectral density from Srm = 0.25 − 2.25 V/√Hz.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Focused ultrasound; Inertial cavitation; Modulated signals

Investigation of Inertial Cavitation of Sonosensitive and Biocompatible Nanoparticles in Flow - Through Tissue- Mimicking Phantoms Employing Focused Ultrasound - George, Benedikt; Savsek, Ula; Fischer, Dagmar; Ermert, Helmut; Rupitsch, Stefan J. (Current Directions in Biomedical Engineering, 2021)
A promising approach to drug delivery applications for chemotherapeutics is the use of drug carriers to reduce the total amount of cytostatics, minimizing side effects. In addition, the carriers, loaded with the drug, can be guided to the tumorous tissue via the vascular system, which enables a local drug release (LDR). In our case, LDR is activated due to the sonosensitive behavior of the nanocapsules by inertial cavitation (IC) caused by focused ultrasound (FUS). Thereby, IC is excited by employing sound pressures within the recommended limit allowed for diagnostic ultrasound. In order to verify this drug delivery approach for its clinical suitability, a tissue-mimicking flow -through phantom, containing a small vessel, is used. Investigations have shown that the drug releasing cavitation effect associated with the sonosensitive and biocompatible nanocapsules also occurs in fine vessel structures, even in the case of moving particles and vessel diameters dc smaller than the wavelength λ.
CRIS-Team Scopus Importer:2024-12-16
Keywords: flow - through.; Inertial cavitation; nanoparticles; tissue - mimicking phantom

In vitro hemocompatibility and cytotoxicity study of poly(2-methyl-2- oxazoline) for biomedical applications - Bauer, Marius; Schroeder, Susann; Tauhardt, Lutz; Kempe, Kristian; Schubert, Ulrich S.; Fischer, Dagmar (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
Since poly(2-methyl-2-oxazolines) (PMeOx) attract high attention for the potential use in drug delivery, cytotoxicity, and hemocompatibility of a set of PMeOxs with molar masses in the range from 2 to 20 kDa are systematically investigated under standardized conditions in terms of molar mass, concentration and time dependency. PMeOx polymers are well tolerated in red blood cell aggregation and hemolysis assays without any damaging effects even at high concentrations up to 80 mg/mL. Only in long term cytotoxicity tests PMeOx polymers moderately influence cell viability in a time, concentration, and molar mass dependent manner. Referring to these results it can be concluded that PEtOx could be promising nonionic hydrophilic polymers for many biomedical applications without any cyto- and hemotoxic effects at typically used therapeutic doses. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2020-10-13
Keywords: biocompatibility; hemocompatibility; hydrophilic polymer; poly(2-methyl-2- oxazoline); ring-opening poly-merization

Linear polyethyleneimine: Optimized synthesis and characterization - on the way to "pharmagrade" batches - Tauhardt, Lutz; Kempe, Kristian; Knop, Katrin; Altuntas, Esra; Jaeger, Michael; Schubert, Stephanie; Fischer, Dagmar; Schubert, Ulrich S. (Macromolecular Chemistry and Physics, 2011)
In conclusion, both the hydrolysis in a flask and in a microwave synthesizer results in a degree of hydrolysis above 99%. LPEIs with differentmolar masses (430 g · mol -1 to 8 600 g · mol -1) were synthesized using both methods. However, compared to the conventional heating in a flask, the hydrolysis in amicrowave synthesizer proceeded much faster. Since the batch processing is automated, it ispossible to synthesize larger amounts of LPEI. The fast and efficient hydrolysis and the good heat distribution render the microwave synthesizer to be very energy saving, compared to conventional heating in a flask. Further advantages of a microwave synthesizer are the excellent control of the heating rate and time, making the hydrolysis highly controllable and reproducible. This is important with respect to the development of a certified synthesis method for larger amounts of "pharmagrade" LPEI. The synthesis conditions were optimized to obtain the maximum of side chain cleavage (99%) within the shortest time range. Although incomplete cleavage (>1%) was obtained even by increasing the reaction time and the temperature, the best and most efficient hydrolysis conditions were found to be 130 8C for 1 h using a microwave synthesizer. The maximum concentration of PEtOx, which can be hydrolyzed, was found to be 0.33 g PEtOx per mL 6 M hydrochloric acid. An increase of the concentration led to a decrease of the degree of hydrolysis. A methyl and a proton-initiated LPEI were prepared via the improved protocol. Several parameters, which can be used as specification for a "pharmagrade" pro- duction of LPEI, were identified and systematically investigated. The developed protocol showed a high reproducibility, and the identity and purity of the LPEIs was proven by means of 1H NMR and IR spectroscopy as well as MALDI-TOF- and ESI-Q-TOF-MS. To the best of our knowledge, this contribution contains the first report of a proton-initiated LPEI. Theprimary aminogroup of 4 enables the possibility of a selective end group functionalization of the LPEI. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Electrospray ionization mass spectrometry; Hydrolysis; Linear polyethyleneimine; Matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS); Poly(2-ethyl-2-oxazoline)s

Loading of bacterial nanocellulose hydrogels with proteins using a high-speed technique - Mueller, Astrid; Wesarg, Falko; Hessler, Nadine; Mueller, Frank A.; Kralisch, Dana; Fischer, Dagmar (Carbohydrate Polymers, 2014)
For the loading of the natural biopolymer bacterial nanocellulose (BNC) with drugs, usually an adsorption method has been described. In the present study, a high-speed loading technique based on vortexing was established for the incorporation of proteins in BNC as drug delivery system. Compared to the conventional technique, vortexing accomplished in 10 min the same protein loading capacity as the adsorption method in 24 h with comparable protein distribution and protein stability. Vortex loaded BNC demonstrated a retarded protein release with a lower total amount of released protein after 168 h compared to the adsorption loaded BNC. This was correlated with a densification of the fiber network as shown by electron microscopy and a reduced water holding capacity. These observations offer the possibility to control the drug release by selection of the preparation technique. © 2014 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial nanocellulose; Controlled release; Hydrogel; Protein delivery

Luminomagnetic Eu3 +- and Dy3 +-doped hydroxyapatite for multimodal imaging - Tesch, Annemarie; Wenisch, Christoph; Herrmann, Karl-Heinz; Reichenbach, Juergen R.; Warncke, Paul; Fischer, Dagmar; Mueller, Frank A. (Materials Science and Engineering C, 2017)
Multimodal imaging has recently attracted much attention due to the advantageous combination of different imaging modalities, like photoluminescence (PL) and magnetic resonance imaging (MRI). In the present study, luminescent and magnetic hydroxyapatites (HAp) were prepared via doping with europium (Eu3 +) and dysprosium (Dy3 +), respectively. Co-doping of Eu3 + and Dy3 + was used to combine the desired physical properties. Both lanthanide ions were successfully incorporated in the HAp crystal lattice, where they preferentially occupied calcium(I) sites. While Eu-doped HAp (Eu:HAp) exhibits dopant concentration dependent persistent PL properties, Dy-doped HAp (Dy:HAp) shows paramagnetic behavior due to the high magnetic moment of Dy3 +. Co-doped HAp (Eu:Dy:HAp) nanoparticles combine both properties in one single crystal. Remarkably, multimodal co-doped HAp features enhanced PL properties due to an energy transfer from Dy3 + sensitizer to Eu3 + activator ions. Eu:Dy:HAp exhibits strong transverse relaxation effects with a maximum transverse relaxivity of 83.3 L/(mmol·s). Due to their tunable PL, magnetic properties and cytocompatibility Eu:-, Dy:- and Eu:Dy:HAp represent promising biocompatible ceramic materials for luminescence imaging that simultaneously may serve as a contrast agent for MRI in permanent implants or functional coatings.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Contrast agent; Europium; Hydroxyapatite; Luminescence; MRI

Medium supplementation with human, but not fetal calf serum facilitates endocytosis of PLGA nanoparticles by human primary B-lymphocytes via complement opsonization - Pusch, Lennart; Brox, Regine; Cunningham, Sarah; Fischer, Dagmar; Hackstein, Holger (Biochemical and Biophysical Research Communications, 2023)
The “biological identity” of nanoparticles (NPs) is governed by a shell consisting of various biomolecules that is formed upon exposure to biological media, the so-called biomolecule corona. Consequently, supplementation of cell culture media with e.g. different sera is likely to affect interactions between cells and NPs ex-vivo, especially endocytosis. We aimed to investigate the differential impact of human and fetal-bovine serum on the endocytosis of poly (lactic-co-glycolic acid) NPs by human peripheral blood mononuclear cells via flow cytometry. Furthermore, we employed different methods to inhibit endocytosis, providing mechanistic insights. The resulting biomolecule corona was characterized via denaturing gel electrophoresis. We found profound differences between human and fetal bovine serum regarding the endocytosis of fluorescently labeled PLGA nanoparticles by different classes of human leukocytes. Uptake by B-lymphocytes was particularly sensitive. We further present evidence, that these effects are mediated by a biomolecule corona. We demonstrate to our knowledge for the first time that the complement is an important contributor to the endocytosis of non-surface-engineered PLGA-nanoparticles prepared via emulsion solvent evaporation by human immune cells. Our data demonstrates that results obtained with xenogeneic culture supplements such as fetal bovine serum may have to be interpreted with caution.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Biomolecule corona; Complement; Culture medium; Nanoparticles; PLGA

Microparticle-Based Controlled Drug Delivery Systems: From Experiments to Statistical Analysis and Design - Lotter, Sebastian; Bellmann, Tom; Marx, Sophie; Wesinger, Mara; Brand, Lukas; Schäfer, Maximilian; Fischer, Dagmar; Schober, Robert (Proceedings - IEEE Global Communications Conference, GLOBECOM, 2023)
Controlled drug delivery (CDD), the controlled release and delivery of therapeutic drugs inside the human body, is a promising approach to increase the efficacy of drug administration and reduce harmful side effects to the body. CDD has been a major research focus in the field of molecular communications (MC) with the goal to aid the design and optimization of CDD systems with communication theoretical analysis. However, the existing studies of CDD under the MC framework are purely theoretical, and the potential of MC for the development of practical CDD applications remains yet to be shown. This paper presents a step towards filling this research gap. Specifically, we present a novel MC-based model for a specific CDD system in which drugs are embedded into microparticles and released gradually towards the target site. It is demonstrated that the proposed model is able to faithfully reproduce experimental data. Furthermore, statistical analysis is conducted to explore the impact of the microparticle size on the drug release. The presented results reveal the sensitivity of the drug release to changes in the microparticle size. In this way, the proposed model can be used for the design of future microparticle-based CDD systems.
Created from Fastlane, Scopus look-up

Mitoxantrone-loaded zeolite beta nanoparticles: Preparation, physico-chemical characterization and biological evaluation - Grund, Stefan; Doussineau, Tristan; Fischer, Dagmar; Mohr, Gerhard J. (Journal of Colloid and Interface Science, 2012)
This article describes the preparation and the physico-chemical characterization of a new host-guest system consisting of zeolite beta nanoparticles as host and mitoxantrone as guest. The resulting host-guest system mitoxantrone@. beta is characterized in terms of morphology (transmission electron microscopy, dynamic light scattering), structure (powder wide-angle X-ray diffraction, nitrogen sorption), surface charge (ξ-potential measurements), and optical properties (UV-visible absorption, steady-state fluorescence). Mitoxantrone@. beta particles are monodisperse in size with a mean diameter centered around 100. nm. Mitoxantrone guest molecules are adsorbed at the micropore entrances of zeolite host. Resulting nanoparticles retrieve the interesting optical properties of guest molecules with a fluorescence emission band in the near-infrared region. Mitoxantrone loading is comparatively evaluated by three different means (elemental analysis, direct and indirect UV-visible absorption studies) showing a loading level of 6.8. μmol/g. Mitoxantrone@. beta nanoparticles also show a noticeable cytotoxic effect when applied to cancer cells. © 2011 Elsevier Inc.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Cancer; Cytostatics; Host-guest system; Mitoxantrone; Nanoparticles; Zeolites

Multiscale polyethylene fiber – bacterial nanocellulose composites through combined laser fusion and bacterial in situ synthesis - Schlicht, Samuel; Wesinger, Mara; Kaufmann, Anke; Fischer, Dagmar; Drummer, Dietmar (International Polymer Processing, 2025)
Ultra-high molecular weight polyethylene (UHMW-PE) fibers and bacterial nanocellulose (BNC) display exceptional mechanical properties alongside the outstanding tribological properties of UHMW-PE while showing unrestricted biocompatibility. For combining the intrinsic advantages of both materials, the present work demonstrates an approach that integrates the slurry-based laser fusion of PE-polyvinylpyrrolidone (PE-PVP) composites and the subsequent bacterial biosynthesis of nanocellulose. PE-PVP composites exhibiting a fraction of 10 % of UHMW-PE fibers were additively manufactured through the locally selective laser-based layer-wise evaporation and subsequent sintering of aqueous suspensions, yielding fiber composites with a water-soluble matrix. The in situ synthesis of bacterial nanocellulose exploits the gelling and dissolving of high-molecular PVP in aqueous media. By allowing for the infiltration of printed PE-PVP composites with nanocellulose-producing Komagataeibacter xylinus, a multiscale composite of polyethylene fibers and bacterial nanocellulose was obtained, corroborating the infiltration of micrometer-scale PE fibers with nanoscale cellulose fibers. Release experiments using methylene blue confirmed the potentials of PE-BNC composites for drug delivery applications, showing first order sigmoidal release kinetics.

Multiscale polyethylene fiber - nanocellulose fiber composites through laser fusion and bacterial in situ synthesis - Schlicht, Samuel; Wesinger, Mara; Kaufmann, Anke; Rösel, Uta; Fischer, Dagmar; Drummer, Dietmar (Conference of the Polymer Processing Society 2024, 2024)
Ultra-high molecular weight polyethylene (PE-UHMW) fibers and bacterial nanocellulose (BNC) fibers both display exceptional mechanical properties alongside the outstanding tribological properties of PE-UHMW while showing an unrestricted biocompatibility. For combining the intrinsic advantages of both materials, the present work demonstrates an approach that integrates the slurry-based laser fusion of PE- Polyvinylpyrrolidone (PE-PVP) composites and the subsequent bacterial biosynthesis of nanoscopic cellulose fibers. PE-PVP composites exhibiting a fraction of 10% of PEUHMW fibers with a mean length of 5.0 mm were obtained through the locally selective, laser-based layer-wise evaporation and subsequent sintering of aqueous suspensions, yielding long fiber composites with a water-soluble matrix. The in situ synthesis of bacterial nanocellulose exploits the gelling and dissolving of high-molecular PVP in aqueous media, promoting the dispersion of individual fibers. Through the infiltration of the PE-PVP composite with nanocellulose-forming Komagataeibacter xylinus and the subsequent bacterial synthesis of BNC, a multiscale composite of PE- UHMW fibers and BNC fibers was obtained, corroborating the infiltration of micrometer-scale PE fiber composites with nanoscale cellulose fibers, yielding a nanoporous multiscale composite. Release experiments using methylene blue confirmed the potentials of PE-BNC composites for drug delivery applications, showing a sigmoidal release similar to pure nanocellulose.<br

Nanocellulose as a natural source for groundbreaking applications in materials science: Today's state - Klemm, Dieter; Cranston, Emily D.; Fischer, Dagmar; Gama, Miguel; Kedzior, Stephanie A.; Kralisch, Dana; Kramer, Friederike; Kondo, Tetsuo; Lindstrom, Tom; Nietzsche, Sandor; Petzold-Welcke, Katrin; Rauchfuss, Falk (Materials Today, 2018)
Nanocelluloses are natural materials with at least one dimension in the nano-scale. They combine important cellulose properties with the features of nanomaterials and open new horizons for materials science and its applications. The field of nanocellulose materials is subdivided into three domains: biotechnologically produced bacterial nanocellulose hydrogels, mechanically delaminated cellulose nanofibers, and hydrolytically extracted cellulose nanocrystals. This review article describes today's state regarding the production, structural details, physicochemical properties, and innovative applications of these nanocelluloses. Promising technical applications including gels/foams, thickeners/stabilizers as well as reinforcing agents have been proposed and research from last five years indicates new potential for groundbreaking innovations in the areas of cosmetic products, wound dressings, drug carriers, medical implants, tissue engineering, food and composites. The current state of worldwide commercialization and the challenge of reducing nanocellulose production costs are also discussed.
CRIS-Team Scopus Importer:2020-10-13

Nanopartikel: Innovative Anwendungsgebiete in der Diagnostik und vor allem in der Therapie - Fischer, Dagmar; Hilger, Ingrid (Deutsche Apotheker Zeitung, 2014)
CRIS-Team Scopus Importer:2020-10-13

Navigating the bacterial cellulose alternative substrates landscape: a bibliometric study and thematic analysis - Quijano, Luis; Fischer, Dagmar; Rodrigues, Raquel; Wei, Yuanyuan (Cellulose, 2024)
Bacterial cellulose (BC) is a versatile and sustainable biomaterial with applications across various industries, including fashion and medicine. This study presents a bibliometric and thematic analysis of the research landscape surrounding BC production with the use of alternative substrates. The bibliometric review analyzed 198 papers selected via Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA), identifying 62 distinct academic disciplines, 906 keywords categorized into 6 clusters, and 98 journals contributing to the field. Of the dataset, approximately 57.6% of the papers were published in Q1 journals, 18.7% in Q2, 12.1% in Q3, 4.0% in Q4, 3.0% were not Q-ranked, and 4.5% were conference papers. The top 12 journals were all Q1 and held 42.9% of the dataset. Citation records, author networks, and keyword trends were examined using Publish or Perish 8 for citation analysis and VOSViewer for Author Network Analysis and keyword clustering. Thematic analysis identified key applications of BC in health and medicine, industry and materials, food and nutrition, electronics and energy, cosmetics and personal care, and environmental and green technology. Advantages such as high mechanical strength, biocompatibility, and biodegradability were frequently highlighted, making BC a preferred material in sustainability-driven industries. However, high production costs and yield/time limitations remain barriers to commercial adoption. The findings underscore the need for innovative solutions and interdisciplinary collaboration to enhance BC's commercial viability and sustainability. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-12-06
Keywords: Alternative substrates; Applications; Bacterial cellulose; Bibliometric review; Keyword analysis; Thematic analysis

Nichtvirale Gentransfer‐Arzneimittel. Therapie mit synthetischen Vektoren - Fischer, Dagmar; Fahr, Alfred (Pharmazie in Unserer Zeit, 2011)
CRIS-Team Scopus Importer:2020-10-13

Optical detection of nanoparticle agglomeration in a living system under the influence of a magnetic field - Mueller, Robert; Stranik, Ondrej; Schlenk, Florian; Werner, Sebastian; Malsch, Daniell; Fischer, Dagmar; Fritzsche, Wolfgang (Journal of Magnetism and Magnetic Materials, 2015)
Nanoparticles are important in diagnosis and therapy. In order to apply their potential, an understanding of the behavior of particles in the body is crucial. However, in vitro experiments usually do not mimic the dynamic conditions of the in vivo situation. The aim of our work was an in vivo observation of particle transport in chicken egg vessels in the presence of a magnetic field by particle tracking. For that we demonstrate the spatial resolution of our observations in a vein and a temporal resolution by observation of the cardiac cycle in an artery. Microscopic images were recorded in dark field reflection and fluorescence mode.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Agglomeration; Chick area Vasculosa; Magnetic particles; Particle transport

Parallel high-throughput screening of polymer vectors for nonviral gene delivery: Evaluation of structure-property relationships of transfection - Rinkenauer, Alexandra C.; Vollrath, Antje; Schallon, Anja; Tauhardt, Lutz; Kempe, Kristian; Schubert, Stephanie; Fischer, Dagmar; Schubert, Ulrich S. (ACS Combinatorial Science, 2013)
In recent years, "high-throughput" (HT) has turned into a keyword in polymer research. In this study, we present a novel HT workflow for the investigation of cationic polymers for gene delivery applications. For this purpose, various poly(ethylene imine)s (PEI) were used as representative vectors and investigated via HT-assays in a 96-well plate format, starting from polyplex preparation up to the examination of the transfection process. In detail, automated polyplex preparation, complex size determination, DNA binding affinity, polyplex stability, cytotoxicity, and transfection efficiency were performed in the well plate format. With standard techniques, investigation of the biological properties of polymers is quite time-consuming, so only a limited number of materials and conditions (such as pH, buffer composition, and concentration) can be examined. The approach described here allows many different polymers and parameters to be tested for transfection properties and cytotoxicity, giving faster insights into structure-activity relationships for biological activity. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2020-10-13
Keywords: combinatorial workflow; heparin; high-throughput screening; nonviral gene delivery; poly(ethylene imine); polyplex stability; transfection

Paramagnetic, NIR-luminescent Nd3+- and Gd3+-doped fluorapatite as contrast agent for multimodal biomedical imaging - Tesch, Annemarie; Roeder, Robert; Zapf, Maximilian; Ronning, Carsten; Warncke, Paul; Fischer, Dagmar; Herrmann, Karl-Heinz; Reichenbach, Juergen R.; Mueller, Frank A. (Journal of the American Ceramic Society, 2018)
Combining near infrared (NIR) luminescence and magnetic resonance (MR) contrasts in a crystal host is highly desirable for contrast agents in biomedical imaging technology, as it will enable multimodal imaging processes. In the present work, biocompatible luminescent and paramagnetic fluorapatite (FAp) nanoparticles were prepared via doping with neodymium (Nd3+) and gadolinium (Gd3+), respectively. While Nd3+-doped FAp (Nd:FAp) exhibits dopant concentration-dependent photoluminescence (PL) in the NIR spectral region, Gd3+-doped FAp (Gd:FAp) shows paramagnetic behavior and strong transverse relaxation effects resulting in MR contrastive properties. Remarkably, multimodal co-doped FAp (Nd:Gd:FAp) nanoparticles combine both properties in 1 single crystal enabling luminescence as well as MR contrast.
CRIS-Team Scopus Importer:2020-10-13
Keywords: fluorapatite; luminescence; MRI; rare-earth elements

PEG-functionalized microparticles selectively target inflamed mucosa in inflammatory bowel disease - Lautenschlaeger, Christian; Schmidt, Carsten; Lehr, Claus-Michael; Fischer, Dagmar; Stallmach, Andreas (European Journal of Pharmaceutics and Biopharmaceutics, 2013)
Introduction The systemic therapy of inflammatory bowel diseases (IBD) by oral administration of anti-inflammatory and immunosuppressive agents is characterized by an increased probability of adverse drug reactions. A successful treatment with a simultaneous reduction in adverse events may be achieved by the administration of micro- and nanosized targeted drug delivery systems, which accumulate selectively in inflamed mucosal areas without systemic absorption. We described in a first in vivo study in IBD patients a significantly enhanced, but minor accumulation of non-functionalized poly(lactic-co-glycolic acid) (PLGA) microparticles in ulcerous lesions very recently. Aim The aim of this study was therefore the assessment of an increased targeting potential of different non-, chitosan- and polyethylene glycol (PEG)-functionalized PLGA micro- and nanoparticles to inflamed intestinal mucosa compared to healthy mucosa. Materials and methods For the quantification of nano- and microparticles, fluoresceinamine-labeled-PLGA was synthesized by carbodiimide reaction. Fluorescent chitosan-, PEG-, and non-functionalized PLGA micro- and nanoparticles with mean hydrodynamic diameters of 3000 nm and 300 nm were prepared by solvent evaporation technique. The targeting efficiencies in terms of particle translocation and deposition were investigated in Ussing chamber experiments. Healthy and inflamed macrobiopsies were received from routine endoscopic examinations of patients with IBD as well as control patients. Results One-hundred and one Ussing chamber experiments of patients with IBD (Crohn's disease: n = 7 and ulcerative colitis: n = 9) as well as healthy control patients (n = 5) were performed. Histomorphological and electrophysiological investigations of inflamed mucosal tissues confirmed a significant alteration of mucosal barrier integrity in IBD patients (TER: healthy: 34.1 Ω cm2; inflamed: 21.6 Ω cm2; p = 0.034). In summary, nanoparticles showed an increased translocation and deposition compared to microparticles in healthy and in inflamed mucosa. Chitosan-functionalized particles adhered onto the tissue surface and thus showed the lowest particle translocation and deposition in healthy and inflamed tissues. PEG-functionalized nanoparticles showed the highest translocation through healthy (2.31%) and inflamed mucosa (5.27%). Moreover, PEG-functionalized microparticles showed a significantly increased translocation through inflamed mucosa (3.33%) compared to healthy mucosa (0.55%; p = 0.045). Notably, the particle deposition of PEG-functionalized microparticles was significantly increased in inflamed mucosa (10.8%) compared to healthy mucosa (4.1%; p = 0.041). Conclusions Based on the targeted translocation and deposition to inflamed intestinal mucosa, PEG-functionalized PLGA microparticles were qualified as an innovative drug delivery system. These particles may serve as a selective treatment strategy to inflamed mucosal areas in IBD with the potential to improve therapeutic efficacy and to reduce adverse events.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Colitis; Inflammatory bowel disease; Microparticles; Nanomedicine; Targeted drug delivery; Ussing chamber

PEG-PLGA nanoparticles deposited in Pseudomonas aeruginosa and Burkholderia cenocepacia - Tchatchiashvili, Tinatini; Duering, Helena; Mueller-Boetticher, Lisa; Grune, Christian; Fischer, Dagmar; Pletz, Mathias W.; Makarewicz, Oliwia (Journal of Pharmaceutical Analysis, 2024)
In our prior research, polymer nanoparticles (NPs) containing tobramycin displayed robust antibacterial efficacy against biofilm-embedded Pseudomonas aeruginosa (P. aeruginosa) and Burkholderia cenocepacia (B. cenocepacia) cells, critical pathogens in cystic fibrosis. In the current study, we investigated the deposition of a nanoparticulate carrier composed of poly(D,L-lactic-co-glycolic acid) (PLGA) and poly(ethylene glycol)-block-PLGA (PEG-PLGA) that was either covalently bonded with cyanine-5-amine (Cy5) or noncovalently bound with freely embedded cationic rhodamine B (RhB), which served as a drug surrogate. After exposing these NPs to bacteria, we performed cell fractionation and fluorescence analysis, which highlighted the accumulation of Cy5 in the outer membranes (OMs) and the accumulation of RhB in the cytoplasm (CP) of cells. The results indicated that these organic NPs are effective vehicles for targeted antibiotic delivery in bacterial cells, explaining the observed increase in the efficacy of encapsulated tobramycin against biofilms. This work emphasizes the potential of PEG-PLGA-based formulations for advanced drug delivery strategies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Antimicrobial activity; Bacterial membrane; Cystic fibrosis; Lipopolysaccharide; Poly(ethylene glycol); Polyester; Tobramycin

PEGylation of Guanidinium and Indole Bearing Poly(methacrylamide)s - Biocompatible Terpolymers for pDNA Delivery - Cokca, Ceren; Hack, Franz J.; Costabel, Daniel; Herwig, Kira; Huelsmann, Juliana; Then, Patrick; Heintzmann, Rainer; Fischer, Dagmar; Peneva, Kalina (Macromolecular Bioscience, 2021)
This study describes the first example for shielding of a high performing terpolymer that consists of N-(2-hydroxypropyl)methacrylamide (HPMA), N-(3-guanidinopropyl)methacrylamide (GPMA), and N-(2-indolethyl)methacrylamide monomers (IEMA) by block copolymerization of a polyethylene glycol derivative - poly(nona(ethylene glycol)methyl ether methacrylate) (P(MEO(9)MA)) via reversible addition-fragmentation chain transfer (RAFT) polymerization. The molecular weight of P(MEO(9)MA) is varied from 3 to 40 kg mol(-1) while the comonomer content of HPMA, GPMA, and IEMA is kept comparable. The influence of P(MEO(9)MA) block with various molecular weights is investigated over cytotoxicity, plasmid DNA (pDNA) binding, and transfection efficiency of the resulting polyplexes. Overall, the increase in molecular weight of P(MEO(9)MA) block demonstrates excellent biocompatibility with higher cell viability in L-929 cells and an efficient binding to pDNA at N/P ratio of 2. The significant transfection efficiency in CHO-K1 cells at N/P ratio 20 is obtained for block copolymers with molecular weight of P(MEO(9)MA) up to 10 kg mol(-1). Moreover, a fluorescently labeled analogue of P(MEO(9)MA), bearing perylene monoimide methacrylamide (PMIM), is introduced as a comonomer in RAFT polymerization. Polyplexes consisting of labeled block copolymer with 20 kg mol(-1) of P(MEO(9)MA) and pDNA are incubated in Hela cells and investigated through structured illumination microscopy (SIM).
CRIS-Team WoS Importer:2021-08-06

Poly(2-ethyl-2-oxazoline) as Alternative for the Stealth Polymer Poly(ethylene glycol): Comparison of in vitro Cytotoxicity and Hemocompatibility - Bauer, Marius; Lautenschlaeger, Christian; Kempe, Kristian; Tauhardt, Lutz; Schubert, Ulrich S.; Fischer, Dagmar (Macromolecular Bioscience, 2012)
Limitations of PEG in drug delivery have been reported from clinical trials. PEtOx (0.4-40kDa) as alternative is synthesized by a living, microwave-assisted polymerization, and is directly compared to PEG of similar molar mass regarding cytotoxicity and hemocompatibility. In short-term treatments, both types of polymers are well tolerated even at high concentrations. Moderate concentration and molar mass dependent cytotoxic effects occurred only after long-term incubation at concentrations higher than therapeutic doses. PEtOx possesses not only an easy route of synthesis and beneficial physicochemical characteristics such as low viscosity and high stability, which are advantageous over PEG, but additionally in vitro toxicology comparable to PEG. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biocompatibility; Hydrophilic polymers; Poly(2-oxazoline)s; Poly(ethylene glycol)s; Stealth effect

Polyelectrolyte complexes of DNA and linear PEI: Formation, composition and properties - Perevyazko, Igor Y.; Bauer, Marius; Pavlov, Georges M.; Hoeppener, Stephanie; Schubert, Stephanie; Fischer, Dagmar; Schubert, Ulrich S. (Langmuir, 2012)
In the present study, the complexation between linear 13.4 kDa poly(ethylene imine) (LPEI) and plasmid DNA was investigated. Analytical ultracentrifugation (AUC) was used for size and molar mass determination. Additionally, the morphology was studied by scanning force microscopy. The polyplex formation was investigated in a wide range of PEI nitrogen to DNA phosphate ratios (N/P). At N/P ratios below 1, the PEI/DNA complex formation is characterized by an incomplete DNA condensation and the formation of the primary DNA/PEI complexes. The merging of the initially formed polyplexes occurs at N/P ∼2, resulting in the formation of polyplexes with much larger size and high aggregation rate. Stable and uniform polyplexes were formed at N/P > 10, with average sizes of the polyplexes of about 170 ± 65 nm. The content of uncomplexed PEI chains in the polyplex dispersion was estimated at four different N/P ratios, 6.2, 11.6, 28.6, and 57.8, by combining preparative centrifugation with a copper complex assay and by sedimentation velocity analysis as an alternative method. It is demonstrated that virtually all added PEI binds to the DNA at N/P < 2.5; further addition of PEI results in the appearance of a large amount of free PEI in solution. Nevertheless, PEI is able to bind in the whole range of N/P ratios tested. According to the data collected by sedimentation velocity analysis and scanning force microscopy, the single PEI/DNA complexes are composed on average of 8 to 32 single condensed DNA plasmids and 70 ± 25 PEI molecules. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2020-10-13

Polyelectrolyte layer assembly of bacterial nanocellulose whiskers with plasmid DNA as biocompatible non-viral gene delivery system - Poetzinger, Yvette; Rabel, Martin; Ahrem, Hannes; Thamm, Jana; Klemm, Dieter; Fischer, Dagmar (Cellulose, 2018)
The nanocrystalline fraction of the natural biopolymer bacterial nanocellulose (BNC) was isolated by controlled degradation resulting in anionic surface modifications. The potential of those nanowhiskers for safe and efficient gene delivery was tested using electrostatic layer assemblies with different poly(ethylene imine)s (2.5 and 25 kDa) and plasmid DNA. For different isolation techniques (sulfuric acid hydrolysis and oxidation) the influence of varying preparation conditions such as concentration of the degrading agent, reaction time and temperature on the physicochemical characteristics of the nanowhiskers like morphology, size, and surface charge could be demonstrated. All nanowhiskers were found to be highly cyto- and hemo-compatible in vitro in short-term (2–8 h) or long-term (24–72 h) studies as well as ex ovo in a shell-less hen’s egg model over 8 h. The use of a polyelectrolyte layer technique based on electrostatic interactions with different poly(ethylene imine)s and plasmid DNA enabled the formation of small sized (ca. 200 nm), DNA stabilizing nanowhiskers and facilitated the transfection of CHO-K1 cells with high biocompatibility. In conclusion, by the use of BNC as sustainable raw material, in combination with optimized and controllable preparation conditions and surface modifications, BNC nanowhiskers modified by a polyelectrolyte layer approach could be used as renewable, “green” drug delivery system for bioactive substances such as nucleic acids.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial nanocellulose; Biocompatibility; Gene delivery; Nanowhiskers; Polyelectrolyte layer

Polyester-based particles to overcome the obstacles of mucus and biofilms in the lung for tobramycin application under static and dynamic fluidic conditions - Ernst, Julia; Klinger-Strobel, Mareike; Arnold, Kathrin; Thamm, Jana; Hartung, Anita; Pletz, Mathias W.; Makarewicz, Oliwia; Fischer, Dagmar (European Journal of Pharmaceutics and Biopharmaceutics, 2018)
Pulmonary infections with Pseudomonas aeruginosa and Burkholderia cepacia complex (Bcc) are difficult to treat and related with high mortality in some diseases like cystic fibrosis due to the recurrent formation of biofilms. The biofilm formation hinders efficient treatment with inhaled antibiotics due to a low penetration of the antibiotics through the polyanionic biofilm matrix and increased antimicrobial resistance of the biofilm-embedded bacteria. In this study, tobramycin (Tb) was encapsulated in particles based on poly(D,L,-lactide-co-glycolide) (PLGA) and poly(ethylene glycol)-co-poly(D,L,-lactide-co-glycolide) diblock (PEG-PLGA) to overcome the biofilm barrier with particle sizes of 225–231 nm (nanoparticles) and 896–902 nm (microparticles), spherical shape and negative zeta potentials. The effectiveness against biofilms of P. aeruginosa and B. cepacia was strongly enhanced by the encapsulation under fluidic experimental condition as well as under static conditions in artificial mucus. The biofilm-embedded bacteria were killed by less than 0.77 mg/l encapsulated Tb, whereas 1,000 mg/l of free Tb or the bulk mixtures of Tb and the particles were ineffective against the biofilms. Moreover, encapsulated Tb was even effective against biofilms of the intrinsically aminoglycoside-resistant B. cepacia, indicating a supportive effect of PEG and PLGA on Tb. No cytotoxicity was detected in vitro in human lung epithelial cells with any formulation.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biofilm; Burkholderia cepacia; Cystic fibrosis; Nanoparticle; Polyester polymer; Pseudomonas aeruginosa; Tobramycin

Poly(ethylene glycol) in drug delivery: Pros and cons as well as potential alternatives - Knop, Katrin; Hoogenboom, Richard; Fischer, Dagmar; Schubert, Ulrich S. (Angewandte Chemie International Edition, 2010)
All-round talent PEG? Poly(ethylene glycol) (PEG) surrounds us in our everyday lives and, particularly in drug-delivery applications, counts as a gold standard. This omnipresent polymer is explored from different angles-advantages and disadvantages are evaluated together with alternative polymers. Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Drug delivery; Nanotechnology; Poly(ethylene glycol); Polymers; Stealth effect

Poly(ethylene glycol) or poly(2-ethyl-2-oxazoline) – A systematic comparison of PLGA nanoparticles from the bottom up - Dirauf, Michael; Grune, Christian; Weber, Christine; Schubert, Ulrich S.; Fischer, Dagmar (European Polymer Journal, 2020)
In times of drastically increasing numbers of scientific reports dealing with the drawbacks of poly(ethylene glycol) (PEG), the search of PEG alternatives has never been more urgent. This study describes a one–to–one comparison of poly(2-ethyl-2-oxazoline)-b-poly(lactic-co-glycolic acid) (PEtOx-b-PLGA) to commercial PEG-b-PLGA from the bottom up in order to verify the similarity of both polymer classes when applied in nanoparticle formulation processes. For this purpose, a library of block copolymers with molar masses (Mn) ranging from 6500 to 60,000 g mol−1 was synthesized via tin-(II)-ethyl hexanoate (SnOct2) catalyzed ring-opening polymerization (ROP) of lactide and glycolide utilizing PEtOx-OH as a macroinitiator in the melt. The PEtOx-b-PLGA polymers were adjusted in terms of molar mass, dispersity and lactide to glycolide ratio of the PLGA block. Nanoparticle formulations showed a similar behavior for both polymer libraries. Zeta potentials as well as hydrodynamic diameter measured by laser light scattering were in excellent agreement, demonstrating the eligibility of PEtOx-b-PLGA as an alternative to formulate “stealth” nanoparticles.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Block copolymer; Nanoparticle; PLGA; Poly(2-oxazoline); Poly(ethylene glycol); Polyester

Poly(ethyleneimines) in dermal applications: biocompatibility and antimicrobial effects. - Wiegand, Cornelia; Bauer, Marius; Hipler, Uta-Christina; Fischer, Dagmar (International Journal of Pharmaceutics, 2013)
Cationic polyamines, such as poly(ethyleneimines) (PEIs), may recommend themselves for antimicrobial applications as they can interact with microbial membranes resulting in their disruption. The purpose of the study was the assessment of biocompatibility and antibacterial activity of PEIs with different architectures (branched (b) and linear (l)) and molar masses (0.8-750 kDa). lPEI and bPEI exhibited a strong antibacterial activity against Staphylococcus aureus and Escherichia coli with a more pronounced effect on the Gram-positive bacteria. lPEIs further demonstrated a higher antibacterial efficacy compared to bPEIs but no significant differences between 5 and 25 kDa were observed. In accordance, antibacterial activity of bPEI did not specifically depend on molar mass. Only slightly lower minimal inhibitory concentrations (MIC) were observed at 5 kDa (S. aureus) and 25 kDa (E. coli) in the tests. As PEIs are compelling candidates for use in antimicrobial treatment, two basic aspects have to be investigated: treatment effectiveness and safety. PEIs clearly induced molecular weight dependent cytotoxic effects in vitro. PEIs with low molecular weight (0.8 and 5 kDa) exhibited higher biocompatibility. Nonetheless, the results confirmed a low genotoxic potential of lPEI and bPEIs. In conclusion, 2.5 kDa-lPEI and 0.8 kDa-bPEI can be recommended for use as antimicrobial polymers in dermal applications due to their high biocompatibility with concomitant antibacterial efficacy. Copyright © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2020-10-13

Polymeric Drug Delivery Systems for Encapsulating Hydrophobic Drugs - Fischer, Dagmar (Drug Delivery Strategies for Poorly Water-Soluble Drugs, 2013)
Summary: The second chapter on polymeric drug delivery systems focuses on techniques that produce particles by in situ polymerization of monomers. It provides a description of the preparation techniques, followed by a discussion of nanospheres and nanocapsules produced by these techniques. The effect of formulation components and process parameters on particle morphology is also covered. Finally, toxicological aspects for in vivo application and scale-up aspects are highlighted. This edition first published 2013 © 2013 John Wiley & Sons, Ltd..
CRIS-Team Scopus Importer:2020-10-13
Keywords: Emulsion polymerization; In situ polymerization; Interfacial condensation; Interfacial polymerization; Miniemulsion; Nanocapsules; Nanospheres; Radical polymerization; Tank reactors

Polymers in drug delivery-state of the art and future trends - Grund, Stefan; Bauer, Marius; Fischer, Dagmar (Advanced Engineering Materials, 2011)
Advances in biotechnology, proteomics, and genomics, as well as the deeper understanding of the molecular and cellular bases of pathophysiological states, have allowed the development of novel drugs such as proteins, peptides, and nucleic acids as therapeutic strategies of the future. Their application, however, requires sophisticated drug delivery systems which can be used to alter the pharmacokinetics and release characteristics of drugs, and to increase tissue specificity and biocompatibility. In this context, polymers provide the most promising avenue in drug release control due to their favorable, adjustable characteristics, and possibilities for further modification. Advances in the biomedical sciences have had a significant impact on the design and development of new and intelligent drug delivery systems for more controlled and targeted drug application. This review summarizes the status quo of polymer use for drug delivery with a special focus on structure-property relationships and gives overviews of various polymers, the relevant parameters in drug delivery and the most promising trends in the future. Advances in biotechnology, proteomics and genomics, and the deeper understanding of the molecular and cellular bases of pathophysiological states, have allowed the development of novel drugs such as proteins, peptides, and nucleic acids as therapeutic strategies. Their application requires sophisticated delivery systems which can be used to alter the pharmacokinetics and release characteristics of drugs, and to increase tissue specificity and biocompatibility. This review summarizes the status quo of polymer use for drug delivery with a focus on structure-property relationships and gives overviews of various polymers, the relevant parameters in drug delivery and the most promising trends in the future. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-10-13

Polysaccharide Nanoparticles Bearing HDAC Inhibitor as Nontoxic Nanocarrier for Drug Delivery - Lindemann, Henry; Kuehne, Marie; Grune, Christian; Warncke, Paul; Hofmann, Susanne; Koschella, Andreas; Godmann, Maren; Fischer, Dagmar; Heinzel, Thorsten; Heinze, Thomas (Macromolecular Bioscience, 2020)
The histone deacetylase inhibitors (HDACi) are potent drugs in the treatment of inflammatory diseases and defined cancer types. However, major drawbacks of HDACi, such as valproic acid (VPA), are limited serum half-life, side effects and the short circulation time. Thus, the immobilization of VPA in a polysaccharide matrix is used to circumvent these problems and to design a suitable nanocarrier system. Therefore, VPA is covalently attached to cellulose and dextran via esterification with degree of substitution (DS) values of up to 2.20. The resulting hydrophobic polymers are shaped to spherical nanoparticles (NPs) with hydrodynamic diameter between 138 to 221 nm and polydispersity indices from 0.064 to 0.094 by nanoprecipitation and emulsification technique. Lipase treatment of the NPs leads to in vitro release of VPA and hence to an inhibition of HDAC2 activity in a HDAC2 assay. NPs are rapidly taken up by HeLa cells and mainly localize in the cytoplasm. The NPs are hemocompatible and nontoxic as revealed by the shell-less hen’s egg model.
CRIS-Team Scopus Importer:2020-10-13
Keywords: drug delivery system; HDAC inhibitor; nanoparticles; polysaccharides; valproic acid

Process control and scale-up of modified bacterial cellulose production for tailor-made anti-inflammatory drug delivery systems - Beekmann, Uwe; Schmolz, Lisa; Lorkowski, Stefan; Werz, Oliver; Thamm, Jana; Fischer, Dagmar; Kralisch, Dana (Carbohydrate Polymers, 2020)
Bacterial cellulose (BC) has proven its high potential as active wound dressing and drug delivery system in many scientific studies, but the transferability of the methods to efficient manufacturing still needs to be demonstrated. This study presents a technically feasible, straightforward and efficient approach to modify BC according to specific medical requirements, to scale-up the cultivation and to load the active pharmaceutical ingredient of interest. By means of in situ-modification of the network structure using water-soluble poly(ethylene glycol) 400 and 4000 on pilot-scale, up to 41.5 ± 3.0 % higher transparency of the dressing, 40.6 ± 3.8 % increased loading capacity and 9% increased total release of the anti-inflammatory model drug diclofenac sodium could be obtained. Spray loading was investigated as material efficient alternative to absorption loading allowing a significant reduction in loading time.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Anti-inflammatory; Bacterial cellulose; Diclofenac; Drug delivery system; Manufacturing; Modification; Scale-up

Prototype of a Coupling Device to Investigate Focused Ultrasound-Induced Inertial Cavitation for Drug Delivery Applications - George, Benedikt; Wittenbrink, Michel; Rupitsch, Stefan J.; Savešk, Ula; Koh, Christian; Fischer, Dagmar; Ermert, Helmut (Current Directions in Biomedical Engineering, 2023)
Focused ultrasound (FUS) can be used as a drug delivery application for localized chemotherapy to treat cancer. The effect of ultrasound-induced inertial cavitation is promising to trigger drug release from nanocarriers. To investigate this effect, usually, a passive cavitation detection setup is employed. However, applying such a setup is challenging for in vivo experiments, as the test object may need to be fixed inside the water tank. Thus, we present a prototype of a coupling device that could significantly simplify experiments. Since this setup favors undesired sound wave interference and their resulting exceedance of the Mechanical Index, we additionally investigated different signal lengths. The occurrence of standing waves at a signal length of 44 cycles can both be derived from a changing cavitation activity and our calculations. The appearing interference also results in a mean increase of the cavitation activity by ≈ 5.1 %, verified by our experiments as well.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Coupling device; drug delivery; focused ultrasound; inertial cavitation

Raman-based detection of ciprofloxacin and its degradation in pharmaceutical formulations - Liu, Chen; Mueller-Botticher, Lisa; Liu, Chang; Popp, Jurgen; Fischer, Dagmar; Cialla-May, Dana (Talanta, 2022)
A Raman-based label-free analytical method was developed to detect the antibiotic ciprofloxacin (CIP) in various pharmaceutical formulations in the presence of different matrices (e.g., ear drops, eye drops and infusion solutions). The Raman spectral analysis is performed for semiquantification in the case of a low background Raman signal, i.e., the signal originating from the excipient and carrier substance of the formulation does not interfere with the fingerprint spectrum of ciprofloxacin. In the case of a background spectrum rich in Raman modes originating from the excipient and carrier substance of the formulation, the pharmaceutical formulation is diluted 1:5000, and thus, the background signal is undetectable. Due to the high affinity of ciprofloxacin towards metallic surfaces, surface-enhanced Raman spectroscopy (SERS) is applied to allow for the sensitive detection of ciprofloxacin. Moreover, the developed measurement routine can be applied to monitor the degradation of the active component ciprofloxacin within the pharmaceutical formulation. The developed assay can therefore be extended to the pharmaceutical industry for quality control in assay applications or the preparation of individualized medicines.
CRIS-Team WoS Importer:2022-08-26

Rapid formation of plasma protein corona critically affects nanoparticle pathophysiology - Tenzer, Stefan; Docter, Dominic; Kuharev, Joerg; Musyanovych, Anna; Fetz, Verena; Hecht, Rouven; Schlenk, Florian; Fischer, Dagmar; Kiouptsi, Klytaimnistra; Reinhardt, Christoph; Landfester, Katharina; Schild, Hansjoerg; et al. (Nature nanotechnology, 2013)
In biological fluids, proteins bind to the surface of nanoparticles to form a coating known as the protein corona, which can critically affect the interaction of the nanoparticles with living systems. As physiological systems are highly dynamic, it is important to obtain a time-resolved knowledge of protein-corona formation, development and biological relevancy. Here we show that label-free snapshot proteomics can be used to obtain quantitative time-resolved profiles of human plasma coronas formed on silica and polystyrene nanoparticles of various size and surface functionalization. Complex time- and nanoparticle-specific coronas, which comprise almost 300 different proteins, were found to form rapidly (<0.5 minutes) and, over time, to change significantly in terms of the amount of bound protein, but not in composition. Rapid corona formation is found to affect haemolysis, thrombocyte activation, nanoparticle uptake and endothelial cell death at an early exposure time. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-10-13

Recent developments and perspectives on gene therapy using synthetic vectors - Schlenk, Florian; Grund, Stefan; Fischer, Dagmar (Therapeutic Delivery, 2013)
Nonviral vector technology is attracting increasing importance in the biomedical community owing to unique advantages and prospects for the treatment of severe diseases by gene therapy. In this review, synthetic vectors that allow the controlled design of efficient and biocompatible carriers are highlighted. The current benefits, potentials, problems and unmet needs of synthetic gene delivery systems, as well as the strategies to overcome the obstacles are also discussed. Common design principles and structure-activity trends have been established that are important for stable and targeted transport to regions of interest in the body, efficient uptake into cells as well as controlled release of drugs inside the cells, for example, in specialized compartments. The status quo of the use of these systems in preclinical and clinical trials is also considered. © 2013 Future Science Ltd.
CRIS-Team Scopus Importer:2020-10-13

Rethinking the impact of the protonable amine density on cationic polymers for gene delivery: A comparative study of partially hydrolyzed poly(2-ethyl-2-oxazoline)s and linear poly(ethylene imine)s - Bauer, Marius; Tauhardt, Lutz; Lambermont-Thijs, Hanneke M. L.; Kempe, Kristian; Hoogenboom, Richard; Schubert, Ulrich S.; Fischer, Dagmar (European Journal of Pharmaceutics and Biopharmaceutics, 2018)
To gain a more profound insight into the impact of the number and the density of protonable amines on the performance of polycations as non-viral vectors, a series of linear poly(ethylene imine)s (LPEIs) with different numbers of ethylene imine (EI) units was compared to partially hydrolyzed (21 to 86%, 20 kDa) poly(2-ethyl-2-oxazoline)s (PHPEtOxs) with a corresponding number of EI units but with varying densities. PHPEtOx polyplexes demonstrated lower transfection efficiencies than the corresponding LPEIs although having the same number of EI units as LPEI, exhibiting smaller or comparable polyplex diameters, similar zeta potentials, and similar or even preferred cyto- and hemocompatibility profiles. The lower efficiency was found to be related to a lower DNA binding capacity and less efficient protection of plasmid DNA against enzymatic degradation. The direct comparison of both types of polymers revealed that the density of charges within the polymer backbone seems to be more important than the total number of EI units. In conclusion, the reduction of the EI density to produce more biocompatible polyplexes must be critically examined, since the presence of high numbers of EI next to each other seems to have a dramatically higher impact on the transfection efficiency than on the in vitro toxicity.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Gene delivery; Non-viral vector; Poly(2-ethyl-2-oxazoline); Poly(ethylene imine); Polymer; Transfection

Scalable 3D Screen Printing Technology in Pharmaceutical Manufacturing - High Degree of Freedom in Terms of Drug Choice - Schneeberger, Achim; Seyferth, Stefan; Fischer, Dagmar (Archives of Dentistry, 2021)

Simulation of the long-term fate of superparamagnetic iron oxide-based nanoparticles using simulated biological fluids - Rabel, Martin; Warncke, Paul; Gruettner, Cordula; Bergemann, Christian; Kurland, Heinz-Dieter; Mueller, Robert; Dugandzic, Vera; Thamm, Jana; Mueller, Frank A.; Popp, Juergen; Cialla-May, Dana; Fischer, Dagmar (Nanomedicine, 2019)
Aim: To simulate the stability and degradation of superparamagnetic iron oxide nanoparticles (MNP) in vitro as part of their life cycle using complex simulated biological fluids. Materials & methods: A set of 13 MNP with different polymeric or inorganic shell materials was synthesized and characterized regarding stability and degradation of core and shell in simulated biological fluids. Results: All MNP formulations showed excellent stability during storage and in simulated body fluid. In endosomal/lysosomal media the degradation behavior depended on shell characteristics (e.g., charge, acid-base character) and temperature enabling the development of an accelerated stress test protocol. Conclusion: Kinetics of transformations depending on the MNP type could be established to define structure-activity relationships as prediction model for rational particle design.
CRIS-Team Scopus Importer:2020-10-13
Keywords: degradation; long-term fate; lysosome/endosome; prediction model; SPION; stability; superparamagnetic iron oxide nanoparticles

Star-shaped block copolymers by copper-catalyzed azide-alkyne cycloaddition for potential drug delivery applications - Von Der Ehe, Christian; Kempe, Kristian; Bauer, Marius; Baumgaertel, Anja; Hager, Martin D.; Fischer, Dagmar; Schubert, Ulrich S. (Macromolecular Chemistry and Physics, 2012)
Star-shaped poly(μ-caprolactone) is synthesized by ring-opening polymerization and subsequently functionalized with alkyne groups. These are utilized for the attachment of linear poly(ethylene glycol) monomethyl ether azide (mPEG-N 3) and poly(2-ethyl-2-oxazoline) azide (PEtOx-N 3) by copper-catalyzed azide-alkyne cycloaddition (CuAAC). The resulting amphiphilic star-shaped block copolymers are characterized by SEC, MALDI-TOF mass spectrometry, NMR spectroscopy, and DLS. In order to elucidate the potential of both systems as drug carriers their loading capacity is studied with a model system, the hydrophobic dye fat brown RR. Furthermore, erythrocyte aggregation tests provide first indications that the two different star-shaped block copolymers are compatible for potential applications in a biological context. Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-10-13
Keywords: CuAAC; micelles; poly(μ-caprolactone)s; poly(2-ethyl-2-oxazoline)s; star polymers

State of the art: Therapeutical strategies for the treatment of inflammatory bowel disease - Lautenschläger, Christian; Schmidt, Carsten; Fischer, Dagmar; Stallmach, Andreas (Current Drug Therapy, 2013)
Inflammatory bowel disease (IBD), commonly known as Crohn's disease and ulcerative colitis, is a frequently occurring disease in Gastroenterology, which is characterized by a chronic intestinal inflammatory ailment. The therapy of IBD is dominated by the administration of anti-inflammatory and immune-modulating drugs, which suppress the intestinal inflammation and thus improve disease-related symptoms. The enhanced insight and more detailed knowledge about the pathophysiological mechanisms of IBD accelerate the research and development of innovative drugs and new treatment strategies. In the last decades, many evolutionary as well as revolutionary innovations were developed and investigated in clinical trials. This review is believed to give an overview about established and future-orientated treatment approaches, including antisense gene therapy, non-embryonic stem cell therapy, leucocytapheresis and faecal biotherapy. Additionally, this review illuminates other smaller clinical trials, which follow interesting and maverick approaches, like lecithinmediated mucosal healing, Trichuris suis ova-supported treatment or several herbal treatment strategies. The main focus is pointed in the conceivable explanation of the respective molecular target mechanisms as well as potential to modulate the inflammatory and immunological process. Additionally, this review gives a brief insight in the therapeutical benefits and mediates about the risks of the respective treatment approaches. © 2013 Bentham Science Publishers.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Anti-inflammatory therapy; Crohn's disease; Immune-modulating therapy; Inflammatory bowel disease; Mucosal healing; Ulcerative colitis

Suitability of viability assays for testing biological effects of coated superparamagnetic nanoparticles - Baehring, Franziska; Schlenk, Florian; Wotschadlo, Jana; Buske, Norbert; Liebert, Tim; Bergemann, Christian; Heinze, Thomas; Hochhaus, Andreas; Fischer, Dagmar; Clement, Joachim H. (IEEE Transactions on Magnetics, 2013)
The aim of this study was to establish an in vitro model test system for the analysis of cellular effects of nanoparticles on endothelial cells using the human brain microvascular endothelial cell line HBMEC, a representative of the blood-brain barrier. At first we defined a toxic end point by using superparamagnetic iron oxide nanoparticles coated with cationic substances (polyethylenimine, chitosan, diethylamine ethyl). To study the toxic effects of nanoparticles we evaluated three different viability assays and one cytotoxicity assay for their suitability. We could show that a luminescence-based assay is most promising for an accurate testing, because it is reproducible and unaffected by assay conditions and reagents. © 1965-2012 IEEE.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Iron oxide; superparamagnetic nanoparticle; viability assay

Surface Design Options in Polymer- and Lipid-Based siRNA Nanoparticles Using Antibodies - Gabel, Michael; Knauß, Annkathrin; Fischer, Dagmar; Neurath, Markus; Weigmann, Benno (International Journal of Molecular Sciences, 2022)
The mechanism of RNA interference (RNAi) could represent a breakthrough in the therapy of all diseases that arise from a gene defect or require the inhibition of a specific gene expression. In particular, small interfering RNA (siRNA) offers an attractive opportunity to achieve a new milestone in the therapy of human diseases. The limitations of siRNA, such as poor stability, inefficient cell uptake, and undesired immune activation, as well as the inability to specifically reach the target tissue in the body, can be overcome by further developments in the field of nanoparticulate drug delivery. Therefore, types of surface modified siRNA nanoparticles are presented and illustrate how a more efficient and safer distribution of siRNA at the target site is possible by modifying the surface properties of nanoparticles with antibodies. However, the development of such efficient and safe delivery strategies is currently still a major challenge. In consideration of that, this review article aims to demonstrate the function and targeted delivery of siRNA nanoparticles, focusing on the surface modification via antibodies, various lipid- and polymer-components, and the therapeutic effects of these delivery systems.
CRIS-Team Scopus Importer:2022-12-09
Keywords: antibody; gene delivery; lipid nanoparticle; polymer nanoparticle; siRNA; surface-functionalized nanoparticles; targeted drug delivery

Sustainability in Drug and Nanoparticle Processing - Fischer, Dagmar (Springer Science and Business Media Deutschland GmbH, 2024)
The formulation of drugs in poly(lactic-co-glycolic acid) (PLGA) nanoparticles can be accomplished by various methods, with nanoprecipitation and nanoemulsion being among the most commonly used manufacturing techniques to provide access to high-quality nanomaterials with reproducible quality. Current trends turned to sustainability and green concepts leading to a re-thinking of these techniques, particularly as the conventional solvents for the dissolution of the polymer suffer from limitations like hazards for human health and natural environment. This chapter gives an overview about the different excipients used in classical nanoformulations with a special focus on the currently applied organic solvents. As alternatives, the status quo of green, sustainable, and alternative solvents regarding their application, advantages, and limitations will be highlighted as well as the role of physicochemical solvent characteristics like water miscibility, viscosity, and vapor pressure for the selection of the formulation process, and for particle characteristics. New alternative solvents will be introduced for PLGA nanoparticle formation and compared regarding particle characteristics and biological effects as well as for in situ particle formation in a matrix consisting of nanocellulose. Conclusively, new alternative solvents are available that present a significant advancement toward the replacement of organic solvents in PLGA nanoparticle formulations.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Drug delivery; Nanoparticles; PLGA; Polymer; Sustainability

Sustainable preparation of anti-inflammatory atorvastatin PLGA nanoparticles - Grune, Christian; Zens, Clara; Czapka, Anna; Scheuer, Karl; Thamm, Jana; Hoeppener, Stephanie; Jandt, Klaus D.; Werz, Oliver; Neugebauer, Ute; Fischer, Dagmar (International Journal of Pharmaceutics, 2021)
In the present study, the anti-inflammatory lipophilic drug atorvastatin was encapsulated in poly(D,L-lactide-co-glycolide) (PLGA) using a sustainable method in comparison to the standard emulsion-diffusion-evaporation technique. For the sustainable method the organic solvent ethyl acetate was fully replaced by 400 g/mol poly(ethylene glycol) (PEG 400). Both techniques led to the formation of nanoparticles with comparable sizes of about 170 to 247 nm depending on the polymer type, with monomodal size distribution and negative zeta potential. All nanoparticles demonstrated a high biocompatibility in a shell-less hen's egg model and displayed an anti-inflammatory effect in human monocytes. The use of PEG 400 resulted in plasticizing effects and a lower crystallinity of the PLGA nanoparticles as determined by differential scanning calorimetry and Raman spectroscopy, which correlated with a faster drug release. Interestingly, the particles prepared by the sustainable method showed a crystallinity and drug release kinetics similar to nanoparticles made of PEG-PLGA using the standard method. Conclusively, the sustainable method is a fast and easy to perform technique suitable to prepare atorvastatin-loaded PLGA nanoparticles avoiding toxic and environmentally damaging drawbacks frequently associated with classical organic solvents.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Atorvastatin; Inflammation; Nanoparticle; PLGA; Sustainable method

Tailor-made material characteristics of bacterial cellulose for drug delivery applications in dentistry - Weyell, Peter; Beekmann, Uwe; Kuepper, Christine; Dederichs, Marco; Thamm, Jana; Fischer, Dagmar; Kralisch, Dana (Carbohydrate Polymers, 2019)
Bacterial cellulose (BC) has shown high potential as innovative wound dressing and drug delivery system. Bringing both together, drug-loaded BC was investigated for applications in dental therapies such as dental extraction or mucosal transplantation. Both applications would benefit from a material which degrades under physiological conditions, and from an antibiotic environment. Consequently, periodate-oxidation of BC was investigated to facilitate modified degradation behaviour. A periodate concentration of 0.14 mol/L at ϑ = 25 °C and t = 8 h resulted in a material loss of <10%, but at the same time a sufficient degree of degradation. Additionally, native and oxidised BC loaded with doxycycline was tested for prophylaxis against infection. An in vitro-toxicity test (MTT assay) provided a first confirmation of biocompatibility, whereas agar diffusion tests proved antibiotic efficiency against pathogenic oral bacteria. Release studies of the drug from native and oxidised BC confirmed a comparative biphasic release behaviour.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial cellulose; Degradation; Dentistry; Doxycycline; Drug release

Tetraspanin 5 (Tspan5), a novel gatekeeper of the tumor suppressor dlc1 and myocardin-related transcription factors (mrtfs), controls hcc growth and senescence - Schreyer, Laura; Mittermeier, Constanze; Franz, Miriam; Meier, Melanie; Martin, Dietmar E.; Maier, Kerstin C.; Hübner, Kerstin; Schneider-Stock, Regine; Singer, Stephan; Holzer, Kerstin; Fischer, Dagmar; Ribback, Silvia; et al. (Cancers, 2021)
Human hepatocellular carcinoma (HCC) is among the most lethal and common cancers in the human population, and new molecular targets for therapeutic intervention are urgently needed. Deleted in liver cancer 1 (DLC1) was originally identified as a tumor suppressor gene in human HCC. DLC1 is a Rho-GTPase-activating protein (RhoGAP) which accelerates the return of RhoGTPases to an inactive state. We recently described that the restoration of DLC1 expression induces cellular senescence. However, this principle is not amenable to direct therapeutic targeting. We therefore performed gene expression profiling for HepG2 cells depleted of DLC1 to identify druggable gene targets mediating the effects of DLC1 on senescence induction. This approach revealed that versican (VCAN), tetraspanin 5 (TSPAN5) and N-cadherin (CDH2) were strongly upregulated upon DLC1 depletion in HCC cells, but only TSPAN5 affected the proliferation of HCC cells and human HCC. The depletion of TSPAN5 induced oncogene-induced senescence (OIS), mediated by the p16INK4a/pRb pathways. Mechanistically, silencing TSPAN5 reduced actin polymerization and thereby myocardin-related transcription factor A-filamin A (MRTF-A-FLNA) complex formation, resulting in decreased expression of MRTF/SRF-dependent target genes and senescence induction in vitro and in vivo. Our results identify TSPAN5 as a novel druggable target for HCC.
CRIS-Team Scopus Importer:2021-11-05
Keywords: DLC1; MKL1; MRTF; SRF; TSPAN5

The acylphloroglucinols hyperforin and myrtucommulone A cause mitochondrial dysfunctions in leukemic cells by direct interference with mitochondria - Wiechmann, Katja; Mueller, Hans; Fischer, Dagmar; Jauch, Johann; Werz, Oliver (Apoptosis, 2015)
The acylphloroglucinols hyperforin (Hypf) and myrtucommulone A (MC A) induce death of cancer cells by triggering the intrinsic/mitochondrial pathway of apoptosis, accompanied by a loss of the mitochondrial membrane potential and release of cytochrome c. However, the upstream targets and mechanisms leading to these mitochondrial events in cancer cells remain elusive. Here we show that Hypf and MC A directly act on mitochondria derived from human leukemic HL-60 cells and thus, disrupt mitochondrial functions. In isolated mitochondria, Hypf and MC A efficiently impaired mitochondrial viability (EC50 = 0.2 and 0.9 μM, respectively), caused loss of the mitochondrial membrane potential (at 0.03 and 0.1 μM, respectively), and suppressed mitochondrial ATP synthesis (IC50 = 0.2 and 0.5 μM, respectively). Consequently, the compounds activated the adenosine monophosphate-activated protein kinase (AMPK) in HL-60 cells, a cellular energy sensor involved in apoptosis of cancer cells. Side by side comparison with the protonophore CCCP and the ATP synthase inhibitor oligomycin suggest that Hypf and MC A act as protonophores that primarily dissipate the mitochondrial membrane potential by direct interaction with the mitochondrial membrane. Together, Hypf and MC A abolish the mitochondrial proton motive force that on one hand impairs mitochondrial viability and on the other cause activation of AMPK due to lowered ATP levels which may further facilitate the intrinsic mitochondrial pathway of apoptosis.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Apoptosis; Hyperforin; Leukemia; Mitochondria; Myrtucommulone

The biopolymer bacterial nanocellulose as drug delivery system: Investigation of drug loading and release using the model protein albumin - Mueller, Astrid; Ni, Zhixu; Hessler, Nadine; Wesarg, Falko; Mueller, Frank A.; Kralisch, Dana; Fischer, Dagmar (Journal of Pharmaceutical Sciences, 2013)
Although bacterial nanocellulose (BNC) has reached enormous interest for biomedical applications because of its outstanding material properties, investigations about its potential as drug delivery system are very rare. In the present study, for the first time, the applicability of BNC as drug delivery system for proteins using serum albumin as model drug was systematically investigated. Additionally, never-dried BNC was compared with freeze-dried BNC. For both types of BNC, a dependency of concentration, temperature, time, and preswelling for albumin loading and release could be demonstrated. These findings indicated an overlay of diffusion- and swelling-controlled processes, which could be confirmed by Ritger-Peppas equation. Freeze-dried samples showed a lower uptake capacity for albumin than native BNC, which was found to be related to changes of the fiber network during the freeze drying process as demonstrated by electron microscopy and protein staining experiments. The integrity and biological activity of proteins could be retained during the loading and release processes, which was demonstrated by gel electrophoresis and the use of luciferase as biologically active molecule. In conclusion, hydrophilicity, high biocompatibility, and controllable drug loading and release render BNC an innovative and attractive biopolymer for controlled drug delivery. © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biomaterials; Controlled release; Diffusion; Hydrogels; Protein delivery

The CAM Model—Q&A with Experts - Fischer, Dagmar; Fluegen, Georg; Garcia, Paul; Ghaffari-Tabrizi-Wizsy, Nassim; Gribaldo, Laura; Huang, Ruby Yun Ju; Rasche, Volker; Ribatti, Domenico; Rousset, Xavier; Pinto, Marta Texeira; Viallet, Jean; Wang, Yan; et al. (Cancers, 2023)
The chick chorioallantoic membrane (CAM), as an extraembryonic tissue layer generated by the fusion of the chorion with the vascularized allantoic membrane, is easily accessible for manipulation. Indeed, grafting tumor cells on the CAM lets xenografts/ovografts develop in a few days for further investigations. Thus, the CAM model represents an alternative test system that is a simple, fast, and low-cost tool to study tumor growth, drug response, or angiogenesis in vivo. Recently, a new era for the CAM model in immune-oncology-based drug discovery has been opened up. Although there are many advantages offering extraordinary and unique applications in cancer research, it has also disadvantages and limitations. This review will discuss the pros and cons with experts in the field.
CRIS-Team Scopus Importer:2023-01-20
Keywords: angiogenesis model; drug discovery; immune-oncology; metastasis model; personalized therapy; standard operation procedures; tumor growth

The differences of the impact of a lipid and protein corona on the colloidal stability, toxicity, and degradation behavior of iron oxide nanoparticles - Rabel, Martin; Warncke, Paul; Thuermer, Maria; Gruettner, Cordula; Bergemann, Christian; Kurland, Heinz-Dieter; Mueller, Frank A.; Koeberle, Andreas; Fischer, Dagmar (Nanoscale, 2021)
Aim: In this study, the influence of a serum albumin (SA) and human plasma (HP) derived protein- and lipid molecule corona on the toxicity and biodegradability of different iron oxide nanoparticles (IONP) was investigated. Methods: IONP were synthesized and physicochemically characterized regarding size, charge, and colloidal stability. The adsorbed proteins were quantified and separated by gel electrophoresis. Adsorbed lipids were profiled by ultraperformance liquid chromatography-ESI-tandem mass spectrometry. The biocompatibility was investigated using isolated erythrocytes and a shell-less hen's egg model. The biodegradability was assessed by iron release studies in artificial body fluids. Results: The adsorption patterns of proteins and lipids varied depending on the surface characteristics of the IONP like charge and hydrophobicity. The biomolecule corona modified IONP displayed favorable colloidal stability and toxicological profile compared to IONP without biomolecule coronas, reducing erythrocyte aggregation and hemolysis in vitro as well as the corresponding effects ex ovo/in vivo. The coronas decreased the degradation speed of all tested IONP compared to bare particles, but, whereas all IONP degraded at the same rate for the SA corona, substantial differences were evident for IONP with HP-derived corona depending on the lipid adsorption profile. Conclusion: In this study the impact of the proteins and lipids in the biomolecule corona on the entire IONP application cycle from the injection process to the degradation was demonstrated.
CRIS-Team WoS Importer:2021-05-28

The indirubin derivative 6-bromoindirubin-3′-glycerol-oxime ether (6BIGOE) potently modulates inflammatory cytokine and prostaglandin release from human monocytes through GSK-3 interference - Czapka, Anna; König, Stefanie; Pergola, Carlo; Grune, Christian; Vougogiannopoulou, Konstantina; Skaltsounis, Alexios Leandros; Fischer, Dagmar; Werz, Oliver (Biochemical Pharmacology, 2020)
Indirubin is a natural bis-indole alkaloid contained as active ingredient in the traditional Chinese remedy Danggui Longhui Wan. Indirubin and its 3′-oxime derivatives exhibit anti-cancer and anti-inflammatory properties and they inhibit glycogen synthase kinase (GSK)-3 in cell-free assays where 6-bromoindirubin-3′-oxime (6BIO) is among the most potent analogs. Here, we reveal 6-bromoindirubin-3′-glycerol-oxime ether (6BIGOE) as highly potent derivative able to inhibit pro-inflammatory cytokine, chemokine and prostaglandin (PG) release in human primary monocytes while increasing anti-inflammatory interleukin (IL)-10 levels. 6BIGOE suppressed lipopolysaccharide (LPS)-induced IL-1β and PGE2 release with IC50 of 0.008 and 0.02 µM, respectively, being ≥ 12-fold more potent than 6BIO. The effects of 6BIGOE are mediated via intracellular inhibition of GSK-3, where 6BIGOE again surpassed the effectiveness of 6BIO despite the higher potency of the latter in cell-free GSK-3 activity assays. Side-by-side comparison of 6BIGOE (0.1 µM) with the selective GSK-3 inhibitor SB216763 (5 µM) revealed congruent properties such as enrichment of β-catenin and suppression of cyclooxygenase (COX)-2 protein levels due to GSK–3 inhibition. Metabololipidomics using ultra-performance liquid chromatography-tandem mass spectrometry showed that 6BIGOE selectively decreases pro-inflammatory COX-derived product formation without marked modulation of other lipid mediators. In summary, 6BIGOE is a highly potent indirubin derivative in the cellular context that favorably modulates pro- and anti-inflammatory cytokines as well as COX-2-derived PG via interference with GSK-3.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Cytokine; Glycogen synthase kinase-3; Indirubin; Inflammation; Lipid mediator

The influence of gradient and statistical arrangements of guanidinium or primary amine groups in poly(methacrylate) copolymers on their DNA binding affinity - Tabujew, Ilja; Cokca, Ceren; Zartner, Leon; Schubert, Ulrich S.; Nischang, Ivo; Fischer, Dagmar; Peneva, Kalina (Journal of Materials Chemistry B, 2019)
Herein, we report the first gradient guanidinium containing cationic copolymers and investigate their binding ability to plasmid DNA (pDNA). To understand the effect of different charge distributions and cationic charge sources (primary amines vs. guanidinium group) on (pDNA) binding affinity, we synthesized a library of well-defined statistical cationic copolymers comprising N-(2-hydroxy-propyl)methacrylamide (HPMA) and N-(3-aminopropyl)methacrylamide (APMA) or N-(3-guanidinopropyl)methacrylamide (GPMA) and compared them with gradient polymers containing the same monomers of similar composition. All copolymers were synthesized through aqueous reversible addition-fragmentation chain transfer (aRAFT) polymerization at various monomer ratios by aiming at similar molar masses with low dispersity indices. For the molar mass characterization, in addition to size exclusion chromatography with two different systems, hydrodynamic characterization utilizing analytical ultracentrifugation, viscometry, and accompanied density measurements was conducted. pDNA was used as a model drug to demonstrate the impact of copolymer architecture on binding efficiency. For both HPMA-APMA and HPMA-GPMA copolymers, the gradient distribution demonstrated superior binding and denser packing of pDNA than their statistical counterparts at 20% and lower cationic charge contents. With respect to charge origin, the guanidinium group represented a higher binding efficiency than primary amines with the same nitrogen to phosphate ratio (N/P ratio). Our study demonstrates the profound effect of gradient monomer arrangement on the ability of polyplex formation and reveals the potential for further investigation in gene delivery applications. Gradient guanidinium containing copolymers have great promise for gene delivery applications due to their high affinity toward pDNA even at very low degrees (<20%) of charged monomer content.
CRIS-Team Scopus Importer:2020-10-13

The physical state of lipid nanoparticles influences their effect on in vitro cell viability - Petersen, Silvia; Steiniger, Frank; Fischer, Dagmar; Fahr, Alfred; Bunjes, Heike (European Journal of Pharmaceutics and Biopharmaceutics, 2011)
Although lipid nanoparticles represent potent drug carriers, for many formulations toxicity data are rare. Thus, in this study, the effect of different lipid nanoparticles on the cell viability of L929 mouse fibroblasts was systematically investigated using the MTT assay. The formulations were composed of trimyristin, tristearin or cholesteryl myristate stabilized with poloxamer 188, polysorbate 80, polyvinyl alcohol or a blend of soybean phospholipid and sodium glycocholate. Depending on lipid and storage conditions, the nanoparticles were prepared in different physical states or crystal modifications leading to different particle shapes. The cell viability was influenced considerably by the physical state of the particle matrix with crystalline nanoparticles causing a stronger decrease in viability than the corresponding liquid or liquid crystalline particles. Effects on the cell viability were also related to the type of matrix lipid, stabilizer and the particle shape. However, the effects of differently shaped particles of different polymorphic modifications of crystalline tristearin were comparable. The low viability caused by poloxamer 188-stabilized particles could be correlated with a strong cell uptake which was investigated by confocal laser scanning microscopy. © 2011 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Cell viability; Cytotoxicity; L929 mouse fibroblasts; Lipid nanoparticles; Particle shape; Physical state

Trends in pharmaceutical analysis and quality control by modern Raman spectroscopic techniques - Silge, A.; Weber, Karina; Cialla-May, D.; Müller-Bötticher, L.; Fischer, Dagmar; Popp, Jürgen (Trac-Trends in Analytical Chemistry, 2022)
The application of Raman spectroscopic methods in life science applications has entered a new era due to advances in instrumentation, miniaturization and, most importantly, increased interdisciplinary dialogue between spectroscopists and end users such as clinicians or pharmacists. Advances in laser sampling technologies, optical instruments and data analysis provide new possibilities for optical sensing and chemical imaging. Raman based technologies are being driven by these new developments, opening new applications for advanced pharmaceutical development and manufacturing. Due to, non-destructive and label free quality testing of drug formulations, Raman sensing is of particular interest for process-related aspects in bioprocessing. The trend to personalized medicine, particularly for pediatric and geriatric applications increased the number of prescriptions of individually tailored medicines manufactured in public pharmacies. This article discusses trends and updates of Raman based analytics and how Raman spectroscopic information can create value for modern pharmaceutical applications and processes. The first section reviews Raman modalities that have great potential for on-site applications in the pharmaceutical industry as well as in research and development. The second section provides an overview of innovative Raman spectroscopic devices and the many possibilities in terms of analytical capabilities and sample properties. Photonic data science has been an important driver for Raman based technologies breakthroughs in the last decade and help to standardize Raman spectral analysis, which is discussed in the third section. In the last section we discuss how to translate Raman based innovations into user-friendly on-site applications.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Coherent Raman scattering; On-site application; Pharmaceutical analysis; Raman analytics; Raman spectroscopy; Surface enhanced Raman spectroscopy; UV resonance Raman

Triterpene acids from frankincense and semi-synthetic derivatives that inhibit 5-lipoxygenase and cathepsin G - Koeberle, Andreas; Henkel, Arne; Verhoff, Moritz; Tausch, Lars; Koenig, Stefanie; Fischer, Dagmar; Kather, Nicole; Seitz, Stefanie; Paul, Michael; Jauch, Johann; Werz, Oliver (Molecules, 2018)
Age-related diseases, such as osteoarthritis, Alzheimer’s disease, diabetes, and cardiovascular disease, are often associated with chronic unresolved inflammation. Neutrophils play central roles in this process by releasing tissue-degenerative proteases, such as cathepsin G, as well as pro-inflammatory leukotrienes produced by the 5-lipoxygenase (5-LO) pathway. Boswellic acids (BAs) are pentacyclic triterpene acids contained in the gum resin of the anti-inflammatory remedy frankincense that target cathepsin G and 5-LO in neutrophils, and might thus represent suitable leads for intervention with age-associated diseases that have a chronic inflammatory component. Here, we investigated whether, in addition to BAs, other triterpene acids from frankincense interfere with 5-LO and cathepsin G. We provide a comprehensive analysis of 17 natural tetra- or pentacyclic triterpene acids for suppression of 5-LO product synthesis in human neutrophils. These triterpene acids were also investigated for their direct interference with 5-LO and cathepsin G in cell-free assays. Furthermore, our studies were expanded to 10 semi-synthetic BA derivatives. Our data reveal that besides BAs, several tetra- and pentacyclic triterpene acids are effective or even superior inhibitors of 5-LO product formation in human neutrophils, and in parallel, inhibit cathepsin G. Their beneficial target profile may qualify triterpene acids as anti-inflammatory natural products and pharmacological leads for intervention with diseases related to aging.
CRIS-Team Scopus Importer:2020-10-13
Keywords: 5-lipoxygenase; Boswellic acid; Cathepsin; Frankincense; Microsomal prostaglandin E2 synthase; Triterpene acid

Vaterite-based in situ surface modification and process-dependent biocompatibility of laser sintered polypropylene - Schlicht, Samuel; Campbell, Jack Charlie; Weber, Alexander Christian; Westhoff, Jan; Volodkin, Dmitry; Fischer, Dagmar; Drummer, Dietmar; Vikulina, Anna (Journal of Materials Research and Technology, 2024)
Polypropylene (PP) rapidly gains scientific attention as fatigue-resistant and lightweight tissue repair and implant material, while emerging laser-sintering based methods for PP processing further allow unlimited versatility of PP specimens and often reduced numbers of process steps, substituting traditional manufacturing approaches. Generally, PP is considered biocompatible for a variety of medical applications while showing superior long-term stability, however, thermoplastic processing of polypropylene may induce the formation of cytotoxic degradation products, necessitating its cytotoxicological assessment. In the present study, PP specimens have been fabricated using warm, quasi-isothermal and complementary cold, non-isothermal powder bed fusion (PBF), allowing processing PP at ambient powder bed temperature of 25 °C for minimizing thermal exposure and the formation of decomposition products. The surface of manufactured specimens has been modified with hybrid coatings consisting of mesoporous inorganic microcrystals of vaterite laden with model biomacromolecules, i.e., fluorescently labelled dextran, demonstrating the stable coating and attachment of dextran-loaded vaterite crystals independent of the applied PBF processing regime. Vaterite coating is degradable and enables the opportunity to endow the surface of PP with sustained release functionalities. Both coated and uncoated specimens demonstrated excellent biocompatibility independent of the applied processing regime, as evaluated in an ex ovo shell-less hen’s egg model.
Keywords: powder bed fusion; additive manufacturing; vaterite; drug release; hen’s egg model

Wirkort Gehirn: Wie Arzneistoffe die Blut-Hirn-Schranke überwinden können - Fischer, Dagmar (Deutsche Apotheker Zeitung, 2012)
CRIS-Team Scopus Importer:2020-10-13